Template carbon material, catalyst layer for polymer electrolyte fuel cell, polymer electrolyte fuel cell, and method for manufacturing the template carbon material.
Patent Information
- Application Number
- JP2025059994
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166802000003 
Figure 2026166802000004 
Figure 2026166802000005
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a template carbon material, a catalyst layer for a polymer electrolyte fuel cell, a fuel cell, and a method for manufacturing a template carbon material. [Background technology]
[0002] Mold carbon material is a type of porous carbon material in which the shape of the mold is reversed by heating a mixture of a carbon source and a mold source, coating the surface of the mold with carbon, and then removing the mold.
[0003] The manufacturing method for mold carbon materials involves, for example, using a general-purpose resin such as polyvinyl alcohol as the carbon source and an alkaline earth metal compound such as magnesium oxide as the mold source, thoroughly mixing them, heating them in a non-oxidizing atmosphere at 600°C to 1500°C, and then removing the mold source by some method, such as dissolving it with acid, thereby carbonizing the carbon source and removing the mold source. Since magnesium oxide and calcium oxide can be easily dissolved with hydrochloric acid, sulfuric acid, etc., mold carbon materials using these compounds as mold sources are often considered.
[0004] Furthermore, since the carbon coating process typically involves heat treatment at temperatures of around 600°C to 1500°C, it is also possible to use compounds that chemically transform into magnesium oxide or calcium oxide during this heat treatment process (for example, carbonates, hydroxides, sulfates, etc.) as the mold source. The temperature for heat treatment to carbonize a material is selected according to the purpose. For example, if you want to prepare a highly amorphous porous carbon material containing a large amount of functional groups, a temperature of 600°C to 900°C is selected. If you want to obtain a highly crystalline porous carbon material, the preparation temperature should exceed 1000°C. However, high-temperature treatment that results in the formation of carbides such as calcium carbide or metal acetylides should be avoided. In practice, the maximum temperature for heat treatment to carbonize a material is around 1800°C.
[0005] Casting carbon materials are classified as a type of porous carbon material, equivalent to porous carbon materials (such as activated carbon) produced by so-called activation methods. Porous carbon materials produced by activation methods grow pores inward through oxidative wear from the outside. In contrast, while the outermost surface of casting carbon materials is affected by the manufacturing method, the pore structure inside the material is generally homogeneous, and the pores are generally connected isotropically. This is a structural characteristic of casting carbon materials that is particularly contrasted with the pore structure of porous carbon materials produced by activation methods.
[0006] The isotropically interconnected pore structure of template carbon materials is sometimes referred to as "connecting pores" in the field of polymer electrolyte fuel cells, and it allows for good fluid flow (rapid diffusion) of gases, water, and other fluids within the material. Therefore, template carbon materials are believed to improve power generation performance when used as catalyst supports and are considered promising materials. Furthermore, in principle, template carbon materials produce pores that are a copy and inversion of the template. As a result, it is possible to obtain a highly uniform pore structure ranging from micropores to several tens of nanometers. This is in contrast to the pores formed by activation methods, which are inevitably distributed widely from micropores to mesopores.
[0007] The thickness of the carbon layer in a mold carbon material can be freely controlled by changing the mixing ratio of the mold source and the carbon source, thus offering a high degree of freedom in terms of specific surface area per unit mass. Because template carbon materials are porous carbon materials, they can be used in fields where so-called activated carbon materials are applied, such as adsorbents for selective adsorption of specific gases and molecules with specific structures in the liquid phase; catalyst supports for polymer electrolyte fuel cells where Ketjenbrak is used; electrodes for supercapacitors; and electrode materials for electrolysis of water and metal-air batteries. A field that seems unique to template carbon materials is the use of high diffusivity within the material, which is achieved by utilizing the interconnectedness of isotropic pores.
[0008] Therefore, various studies have been conducted on mold carbon materials. For example, prior art relating to mold carbon materials is known in Patent Documents 1 to 4.
[0009] Patent Document 1 describes a template carbon material to be used as a support for a solid polymer fuel cell catalyst. Patent Document 1 also states the following: The objective is to improve gas diffusion in the cathode when the template carbon material is used as a support for a solid polymer fuel cell catalyst. This can be achieved by obtaining a carbon material with a dendritic structure containing thick branches.
[0010] Patent Document 2 describes mesoporous carbon, such as mold carbon material. Patent Document 2 states the following: The problem concerns the use of existing mesoporous carbon itself or its crushed products, such as mold carbon material. Specifically, while some mesoporous carbon products are said to have excellent dispersibility, they still have particle sizes of 20 μm or more, meaning that coarse particles are present, making it difficult to disperse them sufficiently uniformly in a media when used as a battery material, etc. Furthermore, if the particle size is reduced, the mesopores are destroyed in the process, preventing the material from functioning properly. As a solution, the mesoporous carbon is refined (preferably by wet grinding using a bead mill or ball mill). During this process, the pore volume, pore diameter, and specific surface area are checked while grinding to determine the grinding conditions that result in the desired pore characteristics.
[0011] Patent Document 3 describes a template carbon material that can suppress the decrease in catalyst utilization rate due to flooding and improve power generation performance when power is generated in a highly humid environment. Patent Document 3 states the following: In bottleneck-type pores where flooding is likely to occur, flooding can be suppressed by increasing the minimum diameter of the neck and narrowing the diameter distribution of the neck. Furthermore, a template carbon material having such bottleneck-type pores can be manufactured by using an MgO template with uniform crystallite size as the template source. In this case, if necessary, the MgO template particles may be pre-pulverized, for example, using a ball mill or jet mill, so that the average particle diameter of the MgO template particles is greater than 200 nm and less than 1000 nm, and the ratio of the peak 3 / 4 width to the half-width in the particle size distribution is less than 0.7 (i.e., the width of the particle size distribution is narrowed).
[0012] Patent Document 4 describes a porous carbon material that has a high specific surface area while also having high corrosion resistance. Patent Document 4 states the following: A porous carbon material having a structure containing graphene sheets with few edges and defects in a number of layers or less can achieve high corrosion resistance relative to its specific surface area, exceeding the conventional relationship between specific surface area and corrosion resistance. Furthermore, as a method for producing such a porous carbon material, alumina, which has high catalytic activity for carbon accumulation and a wide range of particle sizes, is used as a template. A carbon layer is coated onto the alumina nanoparticles that serve as the template, and then the template is dissolved and removed to obtain the porous carbon material. The size of the porous carbon material powder is not particularly limited, but a preferred average particle size is 5 to 2000 nm. On the other hand, a preferred size for the alumina nanoparticles is an average particle size of 4 to 50 nm, more preferably 5 to 20 nm, because using alumina nanoparticles with smaller particle sizes can yield a carbon material with a high specific surface area. Furthermore, an alkaline solution is used to dissolve and remove the alumina nanoparticles that serve as the mold. In this case, it is preferable to place the carbon-coated alumina nanoparticles in the alkaline solution and heat-treat it at a heat treatment temperature of 200 to 300°C. At this time, it is preferable to pulverize the carbon-coated alumina nanoparticles in advance in order to ensure uniform contact of the alkaline solution with the sample. [Prior art documents] [Patent Documents]
[0013] [Patent Document 1] Japanese Patent Publication No. 2020-166941 [Patent Document 2] Japanese Patent Publication No. 2021-178772 [Patent Document 3] Japanese Patent Publication No. 2019-12601 [Patent Document 4] Japanese Patent Publication No. 2015-164889 [Overview of the project] [Problems that the invention aims to solve]
[0014] As mentioned above, template carbon materials are used as adsorbents, catalyst supports, and electrode materials, taking advantage of their high fluid diffusivity within the particles. In this case, fluid diffusivity not only within the particles but also between particles is important. In other words, when using template carbon materials for the aforementioned applications, it is a required characteristic that the template carbon material particles are packed as close together as possible while also exhibiting excellent diffusivity of fluids such as gases and water.
[0015] For example, when using a template carbon material as a catalyst support for a polymer electrolyte fuel cell, the diffusibility of gas and water within the catalyst particles is important from the viewpoint of increasing the utilization rate of the catalyst particles supported inside the carbon particles. This is because the reaction gas can easily reach the catalyst particles inside the particles, and the water produced by the reaction can be quickly discharged, preventing the catalyst particles from becoming inoperable due to blockage by water. On the other hand, from a more macroscopic perspective, it is also important that (1) the diffusibility of the supplied gas and (2) the drainage of the produced water are excellent within the catalyst layer. Therefore, the template carbon material used as a catalyst support requires not only fluid diffusibility of gas and water within the particles (inside the particles), but also fluid diffusibility of gas and water between particles (between particles). To achieve high fluid diffusivity, for example, it is necessary that the fluid diffusivity of gas and water is high even when the template carbon material that serves as the catalyst support is close-packed in the catalyst layer. The reason why the close-packed case must be considered is that the template carbon material supporting the catalyst needs to be densely packed in the catalyst layer. If the catalyst layer is excessively thick, the fluid diffusivity of gas and water decreases, so the catalyst layer must be kept to a predetermined thickness. On the other hand, the catalyst layer must contain a predetermined amount of catalyst particles. Since a catalyst support carrying a predetermined amount of catalyst is used, if the goal is to keep the catalyst layer to a predetermined thickness, the catalyst support must be densely packed. In other words, when a template carbon material is applied to the catalyst support, it is necessary to consider not only the fluid diffusivity within the particles of the template carbon material, but also the fluid diffusivity between the densely packed particles of the template carbon material.
[0016] Thus, when using template carbon materials for applications such as adsorbents, catalyst supports, and electrode materials, it is necessary that the template carbon material particles have high fluid diffusivity even when they are packed in the closest possible density.
[0017] However, mold carbon materials obtained by common manufacturing methods (mixing a carbon source and a mold source, heat-treating them, and then removing the mold source) had the following problems:
[0018] One issue is the presence of coarse particles in the template carbon material. When using template carbon material as a support for a solid polymer fuel cell catalyst, for example, if the template carbon material is composed of fine particles, the reaction gas can easily reach the catalyst supported near the center of the particles, resulting in a higher proportion of the supported catalyst that can contribute to the power generation reaction. On the other hand, if the template carbon material is composed of coarse particles, the reaction gas cannot easily reach the catalyst supported near the center of the particles, resulting in a lower proportion of the supported catalyst that can contribute to the power generation reaction. Therefore, the presence of coarse particles in the template carbon material reduces gas diffusion into the particles, leading to a decrease in catalyst utilization and a decline in power generation performance. Similarly, a smaller average particle size of the template carbon material results in better gas diffusion into the particles, thus suppressing the decrease in catalyst utilization and improving power generation performance.
[0019] Another issue is the broad particle size distribution. When using a template carbon material as a support for a polymer electrolyte fuel cell catalyst, for example, if the particle size distribution is uniform, the particle sizes are consistent, so when the catalyst layer is fabricated, the interparticle gaps are maximized even when the particles are packed tightly. As a result, the fluid diffusivity of gas and water in the catalyst layer is high. On the other hand, if the particle size distribution is broad, small particles can get trapped in the gaps between large particles. As a result, the template carbon material is densely packed in the catalyst layer, and the fluid diffusivity of gas and water in the catalyst layer decreases. Consequently, a broad particle size distribution increases the diffusion resistance of gas and water, leading to a decrease in power generation performance.
[0020] To solve the above problems, a commonly considered method is to reduce particle size and control particle size distribution by pulverizing the particles of the template carbon material. However, when the particles of the template carbon material are pulverized using common methods (e.g., wet bead mill, dry bead mill, or jet mill), the pore structure collapses due to damage from pulverization, and the carbon walls are destroyed, resulting in the generation of fragments. These are fine particles (hereinafter referred to as fine powder) with a particle size range of about 1 / 100 to 1 / 10 of the target particle size range. Since fine powder is formed when the carbon walls have collapsed and many edge surfaces are exposed, aggregation is likely to occur through reactions such as dehydration condensation. Therefore, the fine powder causes aggregation among the particles of the template carbon material. As a result, coarse particles (hereinafter referred to as aggregated coarse particles) are generated. This reduces the fluid diffusivity of the template carbon material, and for example, when used as a catalyst support for polymer electrolyte fuel cells, the fluid diffusivity of gas and water in the catalyst layer decreases, leading to a decrease in power generation performance.
[0021] On the other hand, Patent Document 1 describes how to improve the gas diffusivity of a template carbon material by thickening the branches and imparting a dendritic structure. Since the template carbon material in Patent Document 1 has small particle size and an uneven particle size distribution, further improvement in fluid diffusivity when closely packed can be expected.
[0022] Patent Document 2 describes crushing the mold carbon material itself while checking the pore volume, pore diameter, and specific surface area. However, even if the mold carbon material itself is crushed, the mold carbon material does not become smaller in particle size and the particle size distribution is not made uniform, making it difficult to improve fluid diffusivity when the material is closely packed using the technique in Patent Document 2.
[0023] Patent Document 3 describes pre-grinding the MgO mold particles. However, even if the mold source is pre-grinded, the mold carbon material does not become smaller in particle size and the particle size distribution is not made uniform. Therefore, with the technique described in Patent Document 3, it is difficult to improve the fluid diffusivity when the material is close-packed. Specifically, when using MgO template particles as a template source, if only the MgO template particles are pre-ground, the carbon does not coat the MgO crystallites. As a result of the grinding process, the MgO crystallites deform, aggregate, and produce fine powder due to the damage caused by the grinding. This deformation disrupts the pore structure of the template carbon material, causing the pore structure of the template carbon to collapse. Furthermore, the presence of aggregated particles increases the particle size of the template carbon material. In addition, the generation of fine powder results in an uneven particle size distribution. On the other hand, when using a material other than MgO mold particles as a mold source, when the mixture of the carbon source and the mold source is heat-treated, the carbon source carbonizes and the mold source decomposes thermally at the same time, generating MgO (or oxides of metals contained in the mold source, such as alkaline earth metals). Therefore, even if the mold source is crushed beforehand, its particle size is not maintained, and the mold carbon material does not become smaller in particle size or have a uniform particle size distribution.
[0024] Patent Document 4 describes pre-grinding carbon-coated alumina nanoparticles. However, this grinding is intended to uniformly contact the alumina nanoparticles with an alkaline solution in order to improve the efficiency of removing the alumina nanoparticles that serve as the mold. As a result, the mold carbon material is not reduced in particle size and its particle size distribution is not made uniform, making it difficult to improve fluid diffusivity when the material is closely packed using the technique described in Patent Document 4.
[0025] Thus, as described above, conventional mold carbon materials, including those mentioned in Patent Documents 1-4, have room for improvement in fluid diffusivity when closely packed, and further improvements are needed.
[0026] Therefore, the object of this disclosure is to provide a mold carbon material that can achieve high fluid diffusivity even when closely packed, and a method for manufacturing the same. Another objective of this disclosure is to provide a catalyst layer for a polymer electrolyte fuel cell and a polymer electrolyte fuel cell that can achieve high power generation performance. [Means for solving the problem]
[0027] Means for solving the problem include the following aspects. <1> A template carbon material satisfying the following requirements (A), (B), (C) and (D). In the particle size distribution of the template carbon material based on the cumulative passing amount from small particles to large particles obtained by volume-based particle size measurement using a laser light scattering method, with the total cumulative amount taken as 100%, the common logarithm value of the particle diameter when the cumulative passing amount is 50% is defined as the average particle diameter D 50 (μm), the average particle diameter D 50 is less than 5.0 μm. In the particle size distribution of the template carbon material based on the cumulative passing amount from small particles to large particles obtained by volume-based particle size measurement using a laser light scattering method, with the total cumulative amount taken as 100%, the common logarithm values of the particle diameters when the cumulative passing amount is 10%, 50% and 90% respectively are defined as the 10% particle diameter D 10 (μm), the average particle diameter D 50 (μm) 、 and the 90% particle diameter D 90 (μm), (D 90 -D 10 ) / D 50 is less than 1.1. The bulk density is greater than 0.01 g / cm 3 and less than 0.10 g / cm 3 . The BET specific surface area is 500 m 2 / g or more and 2000 m 2 / g or less. <2> The template carbon material according to <1>, wherein the bulk density is greater than 0.05 g / cm 3 and less than 0.10 g / cm 3 . <3> The template carbon material according to <1> or <2>, which further satisfies the following requirement (E). The pore volume ratio V of pores with a pore diameter of 2 to 10 nm in the total pore volume 2-10 is 25% or more and 45% or less, and the pore volume ratio V of pores with a pore diameter of 2 to 50 nm in the total pore volume 2-50 is 45% or more and 75% or less. <4> The average particle diameter D 50is less than 3.5 μm <1> ~ <3> A mold carbon material as described in any one of the items. <5> <1> ~ <4> A catalyst layer for a polymer electrolyte fuel cell comprising a catalyst support made of a template carbon material as described in any one of the items. <6> <5> A polymer electrolyte fuel cell comprising a catalyst layer for polymer electrolyte fuel cells as described above. <7> A method for manufacturing a mold carbon material comprising the following steps 1 to 4. (1) The first step involves mixing the carbon source and the mold source to obtain the mixture. (2) A second step in which the mixture is heat-treated under an inert gas atmosphere to obtain mold carbon. (3) A third step in which the mold carbon is crushed to obtain crushed mold carbon. (4) Fourth step: Remove the mold from the pulverized mold carbon to obtain mold carbon material. <8> In the third step, the particle size distribution of the pulverized mold carbon, obtained by volume-based particle size measurement using the laser light scattering method, is calculated by setting the total cumulative amount to 100% and the common logarithms of the particle size when the cumulative amount is 10%, 50%, and 90%, respectively, as the 10% particle size DA. 10 (μm), average particle size DA 50 (μm) 、 90% particle size DA 90 When (μm), the average particle size DA 50 It is less than 5.0 μm, (DA 90 -DA 10 ) / DA 50 The mold carbon is crushed until the result is less than 1.1. <7> A method for producing the mold carbon material described above. <9> The heating temperature in the second step is 600°C or higher and 1200°C or lower. <7> or <8> A method for producing the mold carbon material described above. <10> The heating temperature in the second step is 800°C or higher and 1100°C or lower. <7> or <8> A method for producing the mold carbon material described above. <11> In the first step, the mixing ratio of the carbon source to the mold source in the mixture is 0.2 or more in molar ratio. <7> ~ <10> A method for producing a mold carbon material according to any one of the items. <12> The following fifth step is further included: <7> ~ <11> A method for producing a mold carbon material according to any one of the items. (5) A fifth step in which, after the fourth step, the mold carbon material is heat-treated in an inert gas atmosphere at a heating temperature of 1000°C to 2600°C. <13> The mold source in the first step is at least one selected from magnesium and alkaline earth metals, oxides, carbonates, sulfates, and hydroxides. <7> ~ <12> A method for producing a mold carbon material according to any one of the items. <14> The mold source in the first step is at least one selected from magnesium and alkaline earth metals, including carbonates, sulfates, and hydroxides. <7> ~ <12> A method for producing a mold carbon material according to any one of the items. <15> The mold source in the first step is at least one selected from magnesium and calcium carbonates, sulfates, and hydroxides. <7> ~ <12> A method for producing a mold carbon material according to any one of the items. <16> The mold source in the first step is at least one selected from magnesium carbonates, sulfates, and hydroxides. <7> ~ <12> A method for producing a mold carbon material according to any one of the items. <17> The mold source in the first step is a magnesium carbonate. <7> ~ <12> A method for producing a mold carbon material according to any one of the items. <18> The carbon source in the first step includes a carbon source that satisfies at least one of the following requirements (a), (b), and (c). <7> ~ <17> A method for producing a mold carbon material according to any one of the items. (a) an aliphatic hydrocarbon compound having two or more carboxyl groups, and having a structure in which two to four carbon atoms are interposed between at least two of the carboxyl groups. (b) A mixture comprising a low molecular weight compound A having two or more functional groups A and a low molecular weight compound B having two or more functional groups B, wherein at least one of the low molecular weight compound A and the low molecular weight compound B is an aromatic compound, and which, upon heating, can be formed by chemical bonding between the functional groups A and B to create a polymer compound in which the low molecular weight compound A and the low molecular weight compound B are alternately bonded. (c) Having at least two oxygen-containing functional groups and at least two nitrogen-containing functional groups, and having a temperature T at which a 5% mass loss is reached in thermogravimetric analysis under an inert atmosphere. 0.05 Aromatic compounds below 200°C. [Effects of the Invention]
[0028] This disclosure provides a mold carbon material capable of achieving high fluid diffusivity even when closely packed, and a method for manufacturing the same. Furthermore, this disclosure provides a catalyst layer for a polymer electrolyte fuel cell and a polymer electrolyte fuel cell that can achieve high power generation performance. [Brief explanation of the drawing]
[0029] [Figure 1] Figure 1 is a schematic diagram showing an example of the general configuration of the fuel cell of this disclosure. [Figure 2] Figure 2 shows scanning electron microscope (SEM) and transmission electron microscope (TEM) images of typical template carbon materials. [Figure 3] Figure 3 shows scanning electron microscope (SEM) and transmission electron microscope (TEM) images of typical activated porous carbon materials. [Figure 4] Figure 4 shows scanning electron microscope (SEM) and transmission electron microscope (TEM) images of representative other porous carbon materials. [Modes for carrying out the invention]
[0030] In this disclosure, a numerical range represented by "~" means a range that includes the numbers before and after "~" as the lower and upper limits. Furthermore, a numerical range that does not include the numbers before and after "~" that are preceded by "greater than" or "less than" means a range that does not include those numbers as the lower or upper limit. In this disclosure, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes, as long as their intended purpose is achieved. In this disclosure, the “proton-conducting electrolyte material” used in the catalyst layer of a fuel cell is also referred to as an “ionomer.” According to the definition of the International Union of Pure and Applied Chemistry (IUPAC), "micropores" also refer to pores with a diameter of less than 2 nm, for example, while "mesopores" refer to pores with a diameter of 2 nm to 50 nm, for example.
[0031] [Casting carbon material] The template carbon material of this disclosure satisfies requirements (A), (B), (C), and (D) described below (preferably requirements (A), (B), (C), and (D), in addition to requirement (E)). The mold carbon material disclosed herein is a mold carbon material that can achieve high fluid diffusivity even when closely packed. The mold carbon material disclosed herein was discovered through the following findings.
[0032] The inventors investigated a mold carbon material that can achieve high fluid diffusivity even when closely packed, and a method for obtaining such a mold carbon material. As a result of their diligent research, the inventors obtained the following findings.
[0033] For a mold carbon material to achieve high fluid diffusivity even when closely packed, it is important that it does not contain coarse particles, has a small average particle size, a uniform particle size distribution, a low bulk density, and a large specific surface area. Furthermore, when mold carbon material obtained through a general manufacturing process is ground using general methods (for example, wet bead mills, dry bead mills, jet mills, etc.), even if the grinding intensity is varied, it is not possible to obtain mold carbon material that does not contain coarse particles, has a small average particle size, a uniform particle size distribution, low bulk density, and a large specific surface area.
[0034] The reason why a mold carbon material free of coarse particles, with a small average particle size, uniform particle size distribution, low bulk density, and large specific surface area cannot be obtained by crushing mold carbon material using conventional methods is because of the presence of coarse particles. The reason why coarse particles still exist despite the grinding process can be considered as follows.
[0035] When the mold carbon material is crushed, the carbon walls collapse, generating fragments that produce fine particles (hereinafter referred to as "fine powder") with a particle size range of about 1 / 100 to 1 / 10 of the target particle size range. Since fine powder consists of collapsed carbon walls and has more exposed edge surfaces, it is prone to aggregation through reactions such as dehydration condensation. As a result, the fine powder causes aggregation among the mold carbon particles, leading to the formation of coarse particles. On the other hand, if grinding is performed at a weak intensity that is unlikely to generate fine powder, coarse particles will not be ground, making it impossible to reduce particle size and achieve a uniform particle size distribution.
[0036] When mold carbon material is crushed using conventional methods, as mentioned earlier, the carbon walls collapse and fine powder is generated. This fine powder then fills the gaps between the coarser particles, increasing the bulk density. Furthermore, when the carbon walls collapse, the interconnected pore structure unique to mold carbon material also collapses. This unique pore structure results in pores that have developed inside the particles like a sponge. Due to this structure, mold carbon material inherently has a large specific surface area. The pore structure of mold carbon material is important for fluid diffusion inside the particles. As one indicator of pore structure development, a large specific surface area indicates that the particle has many pores inside, and therefore, a larger specific surface area leads to higher fluid diffusion inside the particle. Even if the particle size and particle size distribution are adjusted by crushing or other processes, maintaining this large specific surface area is important for exhibiting high fluid diffusion inside the particles.
[0037] In contrast, if the mold carbon is crushed while still containing the mold before the mold is removed, a mold carbon material can be obtained that does not contain coarse particles, has a small average particle size, a uniform particle size distribution, low bulk density, and a large specific surface area. Furthermore, this method suppresses the generation of coarse particles due to agglomeration caused by fine particles, while simultaneously crushing the existing coarse particles, thereby narrowing the particle size distribution and making the particle size uniform. In addition, by suppressing the generation of fine particles, the bulk density is lowered, and by suppressing the breakdown of the pore structure, the specific surface area can be increased.
[0038] From the above findings, it was found that the template carbon material of this disclosure is a template carbon material that does not contain coarse particles, has a small average particle size, a uniform particle size distribution, a low bulk density, and a large specific surface area.
[0039] When the template carbon material of this disclosure is applied, for example, to a catalyst support for a polymer electrolyte fuel cell, the template carbon material of this disclosure does not contain coarse particles and has a small average particle size. Therefore, gases and ionsomers can easily reach the catalyst supported inside the particles and contribute to the power generation reaction. As a result, the utilization rate of the catalyst is increased. Furthermore, because the template carbon material of this disclosure has a uniform particle size distribution, when it forms a catalyst layer, fine particles do not enter the gaps between coarse particles, resulting in larger interparticle gaps. This improves the diffusivity of gas and water in the catalyst layer and reduces reaction resistance. The low bulk density also contributes to the improved diffusivity of gas and water in the catalyst layer. Furthermore, the mold carbon material of this disclosure maintains the large specific surface area inherent in the mold carbon material even after pulverization, and exhibits high gas diffusion within the particles. Therefore, when the template carbon material of this disclosure is applied to a catalyst support for a polymer electrolyte fuel cell, a catalyst support for a polymer electrolyte fuel cell with excellent power generation performance and a polymer electrolyte fuel cell utilizing it can be obtained.
[0040] Herein, in this disclosure, “template carbon material” means “a porous carbon material obtained by forming a composite of carbon and non-carbon substances and then removing the non-carbon substances.” The characteristics of template carbon materials and porous carbon materials other than template carbon materials, from the perspective of their manufacturing methods, are as follows: Specifically, porous carbon materials can be broadly classified into three categories based on their manufacturing method: (1) activated porous carbon materials obtained by activating carbon black, such as activated carbon; (2) molded carbon materials; and (3) other porous carbon materials such as ESCARBON (Nippon Steel Chemical & Material Co., Ltd.'s "ESCARBON MCND"). The differences between these three types of porous carbon are as follows.
[0041] In scanning electron microscope (SEM) images, in the case of template carbon materials, irregularities on the order of several nanometers due to pores are exposed on the surface of the carbon particles (see Figure 2). In contrast, among porous carbon materials other than template carbon materials, activated porous carbon materials obtained by activating carbon black do not have irregularities on the order of several nanometers due to pores exposed on the surface of the carbon particles (see Figure 3). In transmission electron microscope (TEM) images, the template carbon material shows graphene particles on the order of several nanometers randomly oriented (see Figure 2). In contrast, among porous carbon materials other than the template carbon material, the activated porous carbon material obtained by activating carbon black shows graphene particles on the order of several nanometers forming spheres, with the graphene particles oriented circumferentially in the peripheral areas (see Figure 3). Among porous carbon materials other than template carbon materials, other porous carbon materials such as ESCARBON (Nippon Steel Chemical & Material Co., Ltd. "ESCARBON MCND") show a structure in TEM images where graphene on the order of several nanometers is randomly oriented, similar to template carbon (see Figure 4). In addition, these other porous carbon materials have a dendritic structure in SEM images with branch diameters of approximately 50-80 nm and branch lengths of approximately 50-150 nm (see Figure 4). In these respects, they have structures that differ from template carbon materials and other porous carbon materials.
[0042] Thus, the template carbon material is a porous carbon material obtained by forming a composite of carbon and non-carbon substances and then removing the non-carbon substances. The carbon particle surface has irregularities on the order of several nanometers due to pores, and graphene on the order of several nanometers is randomly oriented. Furthermore, it is a porous carbon material that does not have a dendritic structure.
[0043] The details of the template carbon material of this disclosure are described below.
[0044] <Requirement (A): In the particle size distribution of the template carbon material obtained by volume-based particle size measurement using the laser light scattering method, the common logarithm of the particle size when the total cumulative amount is 100% and the cumulative amount is 50% is the average particle size D 50 When the size is (μm), the average particle size D 50 It is less than 5.0 μm. Average particle size D of the mold carbon material 50 If the particle size is less than 5.0 μm, the particles of the template carbon material are sufficiently small and do not contain coarse particles, so the fluid diffusivity within the particles of the template carbon material is sufficiently high. Therefore, the average particle size D of the mold carbon material 50 It must be less than 5.0 μm.
[0045] Average particle size D of the mold carbon material 50 The average particle size D of the template carbon material is preferably less than 3.5 μm. 50 This is because if the particle size is less than 3.5 μm, the fluid diffusivity within the particles of the template carbon material can be further enhanced.
[0046] Average particle size D of the mold carbon material 50 While there is no particular lower limit, a particle size greater than 0.1 μm makes it easier to obtain a template carbon material with a low bulk density. Therefore, the average particle size D of the template carbon material is 50 If the average particle size D of the template carbon material is greater than 0.1 μm, it is easier to obtain a template carbon material with a low bulk density, and the fluid diffusivity between particles of the template carbon material increases. 50 It is preferable that the particle size is greater than 0.1 μm. Furthermore, the average particle size D of the mold carbon material 50 If the average particle size D of the template carbon material is greater than 0.5 μm, the fluid diffusivity between particles can be further enhanced. 50 It is particularly preferable that the particle size is greater than 0.5 μm.
[0047] Thus, the average particle size D of the mold carbon material 50 If the particle size is less than 5.0 μm, the template carbon material exhibits sufficiently high fluid diffusivity.
[0048] Average particle size D of the mold carbon material 50 This is a value measured by the measurement method described in the examples below.
[0049] <Requirement (B): In the particle size distribution of the template carbon material obtained by volume-based particle size measurement using the laser light scattering method, the common logarithms of the particle size when the total cumulative amount is 10%, 50%, and 90%, respectively, are defined as the 10% particle size D. 10 (μm), average particle size D 50 (μm) 、90% particle size D 90 When (μm), (D 90 -D 10 ) / D 50 It is less than 1.1. (D) 90 -D 10 ) / D 50 If the value is less than 1.1, the particle size distribution of the mold carbon material is sufficiently narrow, meaning that the particle size distribution of the mold carbon material is sufficiently uniform. Therefore, when the mold carbon material is packed in close proximity, it is possible to prevent smaller particles from getting into the gaps between larger particles and reducing fluid diffusivity. Therefore, the (D) of the mold carbon material 90 -D 10 ) / D 50 It must be less than 1.1.
[0050] (D) 90 -D 10 ) / D 50 It is preferable that the (D) of the mold carbon material 90 -D 10 ) / D 50 If the value is less than 0.9, it is possible to prevent further reduction in the fluid diffusivity of the mold carbon material.
[0051] (D) 90 -D 10 ) / D 50 There is no particular lower limit to this value, but the smaller the value, the smaller the particle size distribution, and ideally it should be 0.
[0052] Thus, the (D) of the mold carbon material 90 -D 10 ) / D 50 If the value is less than 1.1, the mold carbon material exhibits sufficiently high fluid diffusivity.
[0053] 10% particle size D of the mold carbon material 10 (μm), average particle size D 50 (μm) 、 90% particle size D 90(μm) is a value measured by the measurement method described in the examples below.
[0054] <Requirement (C): Bulk density of 0.01 g / cm³ 3 Larger 0.10 g / cm 3 It is less than. The mold carbon material does not have a three-dimensional granular structure. Therefore, an excessively low bulk density of the mold carbon material indicates the presence of coarse particles. The presence of coarse particles in the mold carbon material reduces the fluid diffusivity within the particles, resulting in a decrease in the overall fluid diffusivity of the mold carbon material. Furthermore, if the bulk density of the template carbon material becomes too low, the volume occupied by the template carbon material per unit volume decreases. Therefore, when using template carbon material for applications such as adsorbents, catalyst supports, and electrode materials, the volume required to fill a predetermined amount of template carbon material becomes larger, leading to larger devices and equipment. In particular, when using template carbon material as a catalyst support in solid polymer fuel cells, if the bulk density of the template carbon material becomes too low, the thickness of the catalyst layer increases. As a result, the gas diffusion and drainage properties in the catalyst layer decrease, leading to a decline in performance. Therefore, the bulk density of the mold carbon material is 0.01 g / cm³. 3 It needs to be larger. The bulk density of the mold carbon material is 0.05 g / cm³. 3 A larger value is preferable. The bulk density of the template carbon material should be 0.05 g / cm³. 3 A larger size would prevent a further decrease in the fluid diffusivity of the mold carbon material.
[0055] On the other hand, if the bulk density of the mold carbon material becomes too high, the voids between carbon particles when the mold carbon material is packed in the closest density become smaller, which reduces the fluid diffusivity of the mold carbon material. Therefore, the bulk density of the mold carbon material is 0.10 g / cm³. 3 It must be less than [a certain value]. The bulk density of the mold carbon material is 0.095 g / cm³. 3Preferably, the bulk density of the mold carbon material is less than 0.095 g / cm³. 3 This is because a value less than this prevents a further decrease in the fluid diffusibility of the mold carbon material.
[0056] Thus, the bulk density of the template carbon material is 0.01 g / cm³. 3 Larger 0.10 g / cm 3 If the value is less than the specified value, the mold carbon material exhibits sufficiently high fluid diffusivity.
[0057] The bulk density of the mold carbon material is a value measured by the measurement method described in the examples below.
[0058] <Requirement (D) BET specific surface area of 500m 2 / g or more 2000m 2 It is less than / g. If the BET specific surface area of the mold carbon material becomes too small, the fluid diffusivity of the mold carbon material decreases. The reason for this is as follows: Because mold carbon material has a large number of pores, it is a material with a large BET specific surface area, and the BET specific surface area of the mold carbon material is approximately 500 m². 2 It is common for it to show a value of approximately / g or higher. Therefore, the BET specific surface area of the template carbon material is 500m². 2 When the amount is smaller than approximately / g, it is thought that the carbon walls are destroyed by pulverization, causing the pore structure to collapse. As a result, the isocentrically connected pores of the template carbon material collapse, reducing the fluid diffusivity inside the particles of the template carbon material. Therefore, the BET specific surface area of the mold carbon material is 500 m². 2 It must be at least / g. The BET specific surface area of the mold carbon material is 600 m². 2 A value of 1 / g or more is preferred. The BET specific surface area of the mold carbon material is 600 m². 2 This is because a value of 1 / g or higher improves the fluid diffusivity within the particles of the template carbon material.
[0059] On the other hand, if the BET specific surface area of the template carbon material is excessively large, the carbon skeleton of the template carbon material will become excessively thinned, which may reduce the mechanical strength. When the mechanical strength decreases, the template carbon material easily collapses, causing generation of fine powder and aggregation due to the generated fine powder, resulting in a non-uniform particle size distribution. As a result, the fluid diffusibility at the time of closest packing is reduced. Accordingly, the BET specific surface area of the template carbon material is 2000 m 2 / g or less. The BET specific surface area of the template carbon material is preferably 1800 m 2 / g or less. This is because when the BET specific surface area of the template carbon material is 1800 m 2 / g or less, it is possible to further prevent the fluid diffusibility of the template carbon material from decreasing.
[0060] As described above, when the BET specific surface area of the template carbon material is 500 m 2 / g or more and 2000 m 2 / g or less, the template carbon material exhibits sufficiently high fluid diffusibility.
[0061] The BET specific surface area of the template carbon material is a value measured by the measurement method described in Examples below.
[0062] <Requirement (E): The pore volume ratio V of pores with a pore diameter of 2 to 10 nm in the total pore volume 2-10 is 25% or more and 45% or less, and the pore volume ratio V of pores with a pore diameter of 2 to 50 nm in the total pore volume 2-50 is 45% or more and 75% or less.> It is preferable that the pore volume ratio V of pores with a pore diameter of 2 to 10 nm in the total pore volume of the template carbon material 2-10 is 25% or more and 45% or less, and the pore volume ratio V of pores with a pore diameter of 2 to 50 nm in the total pore volume 2-50 is 45% or more and 75% or less. When the pore volume ratio V of the template carbon material 2-10 and the pore volume ratio V 2-50 are within the above ranges, the mesopore volume ratio of the template carbon material (that is, the ratio of mesopores to all pores) becomes sufficiently high. Because mesopores have a larger diameter than micropores, fluids such as gases and water can easily diffuse within them. If the mesopore volume ratio of the mold carbon material is sufficiently high, the fluid diffusivity within the particles of the mold carbon material can be further enhanced.
[0063] Pore volume fraction V of the mold carbon material 2-10 A lower limit of 30% is more preferable. Pore volume fraction V of the mold carbon material 2-10 A higher upper limit of 40% is preferable. Pore volume fraction V of the mold carbon material 2-10 If the ratio is between 30% and 40%, the fluid diffusivity within the particles of the mold carbon material can be further enhanced.
[0064] Pore volume fraction V of the mold carbon material 2-50 A lower limit of 50% is more preferable. Pore volume fraction V of the mold carbon material 2-50 A higher upper limit of 70% is preferable. Pore volume fraction V of the mold carbon material 2-50 If the ratio is between 50% and 70%, the fluid diffusivity within the particles of the mold carbon material can be further enhanced.
[0065] Thus, the pore volume fraction V of the mold carbon material 2-10 and pore volume ratio V 2-50 If the above range is maintained, the template carbon material will exhibit higher fluid diffusivity. In addition, it will be possible to maintain the high BET specific surface area of the template carbon material.
[0066] Pore volume fraction V of the mold carbon material 2-10 and pore volume ratio V 2-50 This is a value measured by the measurement method described in the examples below.
[0067] <Application> Applications of the template carbon material disclosed herein include catalyst supports (especially catalyst supports for polymer electrolyte fuel cells), adsorbents, electrode materials, and the like.
[0068] [Method for manufacturing mold carbon material] The method for manufacturing a mold carbon material according to this disclosure comprises the following steps 1 to 4. The method for manufacturing a mold carbon material according to this disclosure may further comprise the following step 5. (1) The first step involves mixing the carbon source and the mold source to obtain the mixture. (2) A second step in which the mixture is heat-treated under an inert gas atmosphere to obtain mold carbon. (3) A third step in which the mold carbon is crushed to obtain crushed mold carbon. (4) Fourth step: Remove the mold from the pulverized mold carbon to obtain mold carbon material. (5) A fifth step in which, after the fourth step, the mold carbon material is heat-treated in an inert gas atmosphere at a heating temperature of 1000°C to 2600°C.
[0069] According to the method for producing the mold carbon material of this disclosure, the above-mentioned mold carbon material satisfying requirements (A), (B), (C), and (D) (preferably requirements (A), (B), (C), and (D), in addition to requirement (E)) can be obtained. However, the method for obtaining the above-mentioned template carbon material of this disclosure that satisfies requirements (A), (B), (C), and (D) (preferably requirements (A), (B), (C), and (D) in addition to requirement (E)) is not limited to the method for manufacturing the template carbon material of this disclosure.
[0070] The details of each step in the method for manufacturing the mold carbon material of this disclosure are described below.
[0071] <1. First step> In this process, the carbon source and the mold source are mixed to obtain a mixture. At this stage, it is preferable that the carbon source and mold source particles are uniformly mixed so that a uniform fired product (i.e., mold carbon) is formed during the second heating step.
[0072] <1-1. Carbon Sources> The carbon source is not particularly limited; it can be any material that, when combined with the mold source described later, is carbonized by the second step of heat treatment to obtain the mold carbon material.
[0073] However, the carbon source preferably includes a carbon source that satisfies at least one of requirements (a), (b), and (c). A carbon source that satisfies at least one of requirements (a) to (c) has a high carbon yield. Therefore, the carbon source is more likely to carbonize and adhere to the mold surface, and even if the carbon walls are thin due to the development of pores, their strength can be further increased. The third step of the grinding method makes it possible to suppress the generation of fine powder that occurs when grinding the mold carbon material in a general way, but when a carbon source that satisfies at least one of requirements (a) to (c) is used, the strength of the carbon walls can be increased. As a result, the generation of fine powder can be suppressed even further. Thus, using a carbon source that satisfies at least one of requirements (a) to (c), a mold carbon material can be easily produced that does not contain coarse particles, has a small average particle size, a uniform particle size distribution, low bulk density, and a large specific surface area. In other words, to produce a mold carbon material that satisfies requirements (A) to (D) (preferably requirements (A) to (E)), a carbon source that satisfies at least one of requirements (a) to (c) is most preferable. However, the carbon source may include carbon sources other than those that satisfy at least one of requirements (a) to (c). The carbon source should preferably contain, for example, 30% by mass or more (preferably 40% by mass or more) of the carbon source that satisfies at least one of requirements (a) to (c) relative to the total carbon source. In addition, carbon sources other than those that satisfy at least one of requirements (a) to (c) include well-known resins used as carbon sources, such as polyvinyl alcohol, polyethylene glycol, and polyacrylic acid.
[0074] In obtaining the template carbon material of this disclosure, the carbon source is most preferably of the following forms, in order from most preferred to least preferred. (1) A configuration in which the carbon source includes only carbon sources that satisfy any one of requirements (a) to (c). (2) A configuration in which the carbon source includes only carbon sources that satisfy two or three of requirements (a) to (c). (3) An embodiment in which the carbon source contains 50% by mass or more (preferably 60% by mass or more) of the total carbon source, wherein the carbon source satisfies at least one of requirements (a) to (c). (4) An embodiment in which the carbon source contains at least 30% by mass (preferably 40% by mass or more) of the total carbon source, wherein the carbon source satisfies at least one of requirements (a) to (c).
[0075] <1-1-1. (a) Aliphatic hydrocarbon compounds having a structure containing two or more carboxyl groups, wherein at least two of the two or more carboxyl groups have two to four carbon atoms interposed between them (hereinafter referred to as "specific structure a")> Oxygen-containing functional groups, particularly carboxyl groups, exhibit a strong affinity for the template source when used as a carbon source. Therefore, using an aliphatic hydrocarbon compound with a molecular structure containing two or more carboxyl groups in a single molecule as a carbon source results in a high carbon yield. Furthermore, in an aliphatic hydrocarbon compound used as a carbon source, a high carbon yield is observed only when at least two of the two or more carboxyl groups are not adjacent to each other, but are flanked by two to four carbon atoms.
[0076] In specific structure a, the number of carbon atoms interposed between at least two of the two or more carboxyl groups is between two and four, but from the viewpoint of improving carbon yield, it is preferable that it is between two and three. Here, the number of carbon atoms interposed between two carboxyl groups does not include the carbon atoms of the carboxyl groups themselves, but rather the number of carbon atoms linked in a straight chain between the two carboxyl groups. In other words, if carbon atoms are linked in a branched manner between two carboxyl groups, the number of carbon atoms interposed between the two carboxyl groups does not include the carbon atoms of the branched portion. For example, if an isopropylene group is interposed between two carboxyl groups, the number of carbon atoms interposed between the two carboxyl groups is 2. Furthermore, if there are three or more carboxyl groups, at least one pair of carboxyl groups may have two to four carbon atoms interposed between them. The hydrocarbon group with two to four carbon atoms interposed between the two carboxyl groups may be an unsaturated hydrocarbon group or a saturated hydrocarbon group.
[0077] In specific structure a, two or more carboxyl groups may form an anhydride. Alternatively, two or more carboxyl groups may form an alkyl metal salt. The aliphatic hydrocarbon compound may be either a saturated or unsaturated aliphatic hydrocarbon compound, as long as it has the specific structure. Furthermore, the aliphatic hydrocarbon compound may be linear, branched, or cyclic, as long as it has the specific structure.
[0078] Among the carbon sources (i.e., aliphatic hydrocarbon compounds) that satisfy requirement (a), aliphatic hydrocarbon compounds having two carboxyl groups include glutaric acid, adipic acid, malic acid, 2-oxoglutaric acid, (1R,3S)-(+)-camphoric acid, (1S,3R)-(-)-camphoric acid, acetylenedicarboxylic acid, adamantanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, and 1,4-cyclohexyl Examples include sandicarboxylic acid, tetrahydrofuran-2,5-dicarboxylic acid, 2-butene-1,4-dicarboxylic acid, 1,2-cyclobutanedicarboxylic acid, 1,2-cyclopropanedicarboxylic acid (anhydride), 1,3-propanedicarboxylic acid (glutaric acid), L-glutamic acid, tartaric acid, itaconic acid, 3,3-dimethylglutaric acid (anhydride), (+)-monosulfate acid (mercaptosuccinic acid), pentendioic acid (Pent-2-ene-1,5-dioic acid), glutaconic acid, fumaric acid, maleic acid, malic acid, citraconic acid (anhydride), aspartic acid, etc.
[0079] Aliphatic hydrocarbon compounds having three carboxyl groups include citric acid, cis-aconitic acid, trans-aconitic acid, 1,2,3-propanetricarboxylic acid (tricarbaryl acid), 1,1,2-propanetricarboxylic acid, propanetricarboxylic acid, 1α,3α,5α-trimethylcyclohexane-1,3,5-tricarboxylic acid, 1,3,5-pentanetricarboxylic acid, cyclohexane-1,3,5-tricarboxylic acid, (1α,2α,4α)-1,2,4-cyclohexanetricarboxylic acid, 1,3,5-pentanetricarboxylic acid, 2-hydroxypropane-1,2,3-tricarboxylic acid (citric acid), and 2-methylcitric acid.
[0080] Aliphatic hydrocarbon compounds having four or more carboxyl groups include mesobutane 1,2,3,4-tetracarboxylic acid and its anhydride, tetrahydrofuran-2,3,4,5-tetracarboxylic acid and its anhydride, 1,2,3,4-cyclobutanetetracarboxylic acid and its anhydride, cyclopropane-1,1,2,2-tetracarboxylic acid and its anhydride, 1,2,3,4-cyclopentanetetracarboxylic acid and its anhydride, adamantane-1,3,5,7-tetracarboxylic acid, and (+)-(18-crown-6)-2,3,11,12-tetracarboxylic acid.
[0081] <1-1-2.(b) A mixture comprising a low molecular weight compound A having two or more functional groups A and a low molecular weight compound B having two or more functional groups B, wherein at least one of the low molecular weight compound A and the low molecular weight compound B is an aromatic compound, and which, upon heating, can be formed in which the functional groups A and B chemically bond and the low molecular weight compound A and the low molecular weight compound B are alternately bonded.>
[0082] By using low-molecular-weight compounds with two or more functional groups capable of forming high-molecular-weight compounds as a carbon source, a high carbon yield can be obtained. The reason for this is as follows: Compounds containing aromatic rings in their structure, when used as a carbon source, remain stable during the carbonization process without decomposing, resulting in a high carbon yield. To prevent the aromatic compound from sublimating and dissipating outside the system during the carbonization process, thus reducing the carbon yield, a low-molecular-weight compound A with functional group A and a low-molecular-weight compound B with functional group B that chemically bonds to functional group A are used as the carbon source. In this way, low-molecular-weight compound A and low-molecular-weight compound B thermally form a chemical bond during the carbonization process. To further increase the molecular weight, low-molecular-weight compound A is selected to have two or more functional group As, and low-molecular-weight compound B has two or more functional group Bs, and low-molecular-weight compound A and low-molecular-weight compound B are selected to be able to alternately bond with each other to form a polymer. In this way, the aromatic compound remains with the template compound even after the carbonization process without sublimation, making it possible to increase the carbon yield. In particular, to further increase the carbonization yield, it is effective to improve the heat resistance of the chemical bond between low molecular weight compound A and low molecular weight compound B. For this purpose, amide bonds, and more specifically, imide bonds, are preferred. Specifically, it is considered that using a carboxyl group for functional group A and an amino group for functional group B forms an amide bond, and using a dicarboxylic acid anhydride for functional group A forms an imide bond, thus increasing the carbon yield, and therefore these are preferred.
[0083] In this context, "low molecular weight compounds" refers to compounds with a molecular weight of 600 or less that are practically applicable, and preferably, compounds with a molecular weight of 100 to 500.
[0084] At least one of low molecular weight compound A and low molecular weight compound B is an aromatic compound, but the combination may be one aromatic compound and the other aliphatic compound, or both low molecular weight compound A and low molecular weight compound B may be aromatic compounds. However, from the viewpoint of improving oxidation resistance and carbonization yield, it is preferable that both low molecular weight compound A and low molecular weight compound B are aromatic compounds. Note that functional group A and functional group B are different functional groups, and low molecular weight compound A and low molecular weight compound B are different compounds.
[0085] Here, aromatic compounds include monocyclic aromatic compounds, polycyclic aromatic compounds with two or more rings, and non-polycyclic aromatic compounds with two or more rings. Note that aromatic compounds also include heterocyclic aromatic compounds.
[0086] Examples of monocyclic aromatic compounds include compounds having a benzene skeleton, a pyridine skeleton, a pyrimidine skeleton, a triazine skeleton, a pyrrole skeleton, a furan skeleton, and the like. Polycyclic aromatic compounds with two or more rings are compounds in which two or more aromatic rings are fused together, and include compounds having a naphthalene skeleton, anthracene skeleton, phenanthrene skeleton, benzoanthracene skeleton, chrysene skeleton, 3,4-benzophenanthrene skeleton, pyrene skeleton, perylene skeleton, anthraquinone skeleton, a skeleton in which the carbon atoms of phenanthrene are replaced with nitrogen atoms (e.g., 1-azaphenanthrene, 4-azaphenanthrene, 9-azaphenanthrene, 4,5-diazaphenanthrene, etc.), and a skeleton in which the carbon atoms of anthracene are replaced with nitrogen atoms (e.g., 9-azaanthracene, 9,10-diazaanthracene, etc.). Non-condensed polycyclic aromatic compounds with two or more rings are formed by two or more aromatic rings directly or by a crosslinking agent (biphenyl or -C(CH)). 2 ) 2 These are compounds linked together by aliphatic hydrocarbon groups such as -S- and -SO4-, oxygen-mediated bridging members such as -O-, and bridging members such as -C=O-, and include compounds having a biphenyl skeleton, a terphenyl skeleton, a diphenylmethane skeleton, a benzophenone skeleton, an oxydiphenyl skeleton, a thiodiphenyl skeleton, and a triphenylmethane skeleton.
[0087] Aliphatic compounds may be linear, branched, or cyclic compounds, and examples include aliphatic hydrocarbon compounds and aliphatic heterocyclic compounds.
[0088] From the viewpoint of improving oxidation resistance and carbonization yield, a preferred combination of functional groups for low molecular weight compounds A and B is one in which functional group A of low molecular weight compound A is an oxygen-containing functional group and functional group B of low molecular weight compound B is a nitrogen-containing functional group. From the viewpoint of improving oxidation resistance and carbonization yield, a combination of functional groups that form amide bonds or imide bonds, which have high thermal stability, is preferred. The oxygen-containing functional group is a hydroxyl group or a carboxyl group, and the nitrogen-containing functional group is an amino group.
[0089] Here, two or more carboxyl groups may form an anhydride. In other words, low molecular weight compound A may have two carboxyl anhydrides as functional groups among two or more functional groups A. Also, two or more carboxyl groups may form an alkyl metal salt.
[0090] The combination of functional groups of low molecular weight compounds A and B is not limited to the above, and may include combinations such as a hydroxyl group A of low molecular weight compound A and an isocyanate group B of low molecular weight compound B, or a carboxyl group A of low molecular weight compound A and a hydroxyl group B of low molecular weight compound B.
[0091] Aromatic compounds having two or more hydroxyl groups include dihydroxyanthracene, 1,3-dihydroxybenzene, 1,4-dihydroxybenzene, 2,6-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,5-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 1,7-dihydroxynaphthalene, 1,2-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, 1,3-dihydroxynaphthalene, 1,3-Dihydroxy-9H-xanthen-9-one, 1,5-Diamino-4,8-dihydroxyanthraquinone, 4,7-dihydroxycoumarin, 6,7-dihydroxycoumarin, and 2,6-dihydroxy Examples include xyanthraquinone, 2,6-dihydroxyanthraquinone, 1,4-dihydroxyanthraquinone, 1,8-dihydroxyanthraquinone, 1,2-dihydroxyanthraquinone, 1,5-dihydroxyanthraquinone, 1,2,4-trihydroxyanthraquinone, 1,3,8-trihydroxy-6-methylanthraquinone, 4,4'-dihydroxybenzophenone, 2,2'-dihydroxybenzophenone, 2,4'-dihydroxybenzophenone, 2,4-dihydroxybenzophenone, 3,4-dihydroxybenzophenone, 4,4'-dihydroxybiphenyl, 2,2'-dihydroxybenzophenone, 2,5-dihydroxybenzophenone, and derivatives of these compounds.
[0092] Aliphatic hydrocarbon compounds having two or more hydroxyl groups include 1,3,5-adamantanetriol, 1,3-adamantanediol, 3-(hydroxymethyl)-1-adamantanol, cis,trans-5,9-cyclododecadiene-cis-1,2-diol, 4,5-dihydroxy-4-cyclopentene-1,2,3-trione, 2,5-dihydroxy-2,5-dimethylhexane, 4,4'-bicyclohexanol, 1,3-cyclopentanediol, di(trimethylolpropane), 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and derivatives of these compounds.
[0093] Aromatic compounds having two or more carboxyl groups include phthalic acid, isophthalic acid, terephthalic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,3,5-benzenetricarboxylic acid, 4,4'-biphenyldicarboxylic acid, 3,3'-biphenyldicarboxylic acid, 2,2'-biphenyldicarboxylic acid, azobenzene-4,4'-dicarboxylic acid, azobenzene-3,3'-dicarboxylic acid, benzophenone-4,4'-dicarboxylic acid, and benzophenone-3,3 Examples include '-dicarboxylic acids, 4,4'-dicarboxydiphenyl ethers, 4,4'-dicarboxydiphenyl sulfones, 2,6-pyridinedicarboxylic acid, 2,5-pyridinedicarboxylic acid, 2,3-pyridinedicarboxylic acid, 3,5-pyridinedicarboxylic acid, anthraquinone-2,3-dicarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, and dianhydrides, biphenyl-3,3',5,5'-tetracarboxylic acid, pyromellitic acid, 3,4,9,10-perylenetetracarboxylic acid, and dianhydrides.
[0094] Aliphatic compounds having two or more carboxyl groups include succinic acid, glutaric acid, adipic acid, malic acid, 2-oxoglutaric acid, (1R,3S)-(+)-camphoric acid, (1S,3R)-(-)-camphoric acid, acetylenedicarboxylic acid, adamantanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, tetrahydrofuran-2,5-dicarboxylic acid, 2-butene-1,4-dicarboxylic acid, 1,2-cyclobutanedicarboxylic acid, 1,2-cyclopropanedicarboxylic acid (anhydride), 1,3-propanedicarboxylic acid (glutaric acid), L-glutamic acid, tartaric acid, itaconic acid, 3,3-dimethylglutaric acid (anhydride), (+)-monosulfate acid (mercaptosuccinic acid), and pentenediic acid (Pent-2-ene-1,5-dicarboxylic acid). (acid), glutaconic acid, fumaric acid, maleic acid, malic acid (malic acid), citraconic acid (anhydride), aspartic acid, cis-aconitic acid, trans-aconitic acid, 1,2,3-propanetricarboxylic acid (tricarbaryl acid), 1,1,2-propanetricarboxylic acid, propanetricarboxylic acid, 1α,3α,5α-trimethylcyclohexane-1,3,5-tricarboxylic acid, 1,3,5-pentanetricarboxylic acid, cyclohexane-1,3,5-tricarboxylic acid, (1α,2α,4α)-1,2,4-cyclohexanetricarboxylic acid, 1,3,5-pentanetricarboxylic acid, 2-hydroxypropane Examples include -1,2,3-tricarboxylic acid (citric acid), 2-methylcitric acid, mesobutane 1,2,3,4-tetracarboxylic acid and its anhydride; tetrahydrofuran-2,3,4,5-tetracarboxylic acid and its anhydride; 1,2,3,4-cyclobutanetetracarboxylic acid and its anhydride; cyclopropane-1,1,2,2-tetracarboxylic acid and its anhydride; 1,2,3,4-cyclopentanetetracarboxylic acid and its anhydride; adamantane-1,3,5,7-tetracarboxylic acid, (+)-(18-crown-6)-2,3,11,12-tetracarboxylic acid and derivatives of these compounds.
[0095] Aromatic compounds having two or more amino groups include melamine, 1,4-phenylenediamine, 1,3-phenylenediamine, 1,2-phenylenediamine, 4,4-oxydianiline, 3,3-oxydianiline, 3,4-oxydianiline, and Bis(4-aminophenyl). Examples include sulfides, o-Tolidine, m-Tolidine, 4,4'-Methylenedianiline, 4,4'-Diamino-p-terphenyl, 2,6-Diaminoanthraquinone, 1,3-Diaminopyrene, 1,6-Diaminopyrene, 3,6-Diaminocarbazole, 3,3'-Diaminobenzophenone, 4,4'-Diaminobenzophenone, 3,3'-Sulfonyldianiline, 4,4'-Sulfonyldianiline, 1,2-Diaminonaphthalene, 2,3-Diaminonaphthalene, 1,5-Diaminonaphthalene, 1,8-Diaminonaphthalene, 1,4-Bis(4-aminophenoxy)-Benzene, 1,3-s(4-aminophenoxy)-Benzene, 9,9-Bis(4-aminophenyl)fluorene, and derivatives of these compounds.
[0096] Aliphatic compounds having two or more amino groups include hexamethylenetetramine, 4,4'-Methylenebis(cyclohexylamine), triethylenediamine, N,N',N''-Trimethyldiethylenetriamine, 1,4,7,10,13,16-Hexaazacyclooctadecane Cyclen, 1,5,9-Triazacyclododecane, 1,4,7-Triazacyclononane, 2,2'-Diamino-4,4'-bithiazole, 4,4'-Methylenebis(cyclohexylamine), 2,3-diamino-2,3-dimethylbutane, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, N,N'-bis(3-aminopropyl)-1,4-butanediamine tetrahydrochloride, Hexahydro-p-xylylenediamine, Hexahydro-m-xylylenediamine, and derivatives of these compounds.
[0097] <1-1-3.(c) Having at least two oxygen-containing functional groups and at least two nitrogen-containing functional groups, and at the temperature T at which a 5% mass loss is reached in thermogravimetric analysis under an inert atmosphere 0.05 contains aromatic compounds below 200℃ Using aromatic compounds containing multiple oxygen-containing or nitrogen-containing functional groups as a carbon source results in a higher carbon yield. This is because the oxygen-containing or nitrogen-containing functional groups in aromatic compounds have a strong affinity for the template source. Furthermore, compounds with aromatic rings in their structure, when used as a carbon source, remain stable without decomposing during the carbonization process, thus resulting in a higher carbon yield.
[0098] In aromatic compounds, the number of oxygen-containing functional groups and nitrogen-containing functional groups in the compound is two or more, but from the viewpoint of improving carbon yield, it is preferable that there are two to six groups, and more preferably two to four groups. Examples of oxygen-containing functional groups include carboxyl groups and hydroxyl groups. Examples of nitrogen-containing functional groups include amino groups.
[0099] In aromatic compounds, the number of carbon atoms interposed between at least two oxygen-containing functional groups or nitrogen-containing functional groups is preferably two or more, more preferably two to five, and most preferably two to four, from the viewpoint of improving carbon yield. Here, the number of carbon atoms interposed between two oxygen-containing or nitrogen-containing functional groups is the number of carbon atoms linearly linked between the two oxygen-containing or nitrogen-containing functional groups, excluding the carbon atoms of the oxygen-containing or nitrogen-containing functional groups themselves (e.g., the carbon atoms of the carboxyl group). In other words, if the carbon atoms interposed between two oxygen-containing or nitrogen-containing functional groups have substituents (e.g., alkyl groups), the number of carbon atoms interposed between the two oxygen-containing or nitrogen-containing functional groups does not include the number of substituent carbon atoms. Furthermore, the number of carbon atoms interposed between two oxygen-containing or nitrogen-containing functional groups is the number of carbon atoms interposed between the closest oxygen-containing or nitrogen-containing functional groups.
[0100] The functional groups contained in aromatic compounds strongly adsorb to the template source, and during the carbonization process, the carbon source undergoes thermal decomposition, and the inorganic compounds of the template source strongly bond with the oxygen or nitrogen-containing functional groups, thereby suppressing the disappearance of the decomposition products of the carbon source in the gas phase. Therefore, it is a prerequisite that the carbon source undergoes thermal decomposition during the carbonization process. In other words, aromatic compounds reach a 5% mass weight loss in thermogravimetric analysis under an inert atmosphere at temperature T 0.05 However, it needs to be filled at a temperature of 200℃ or lower. In this regard, for example, anthraquinone and phenanthrenequinone have two quinone-type oxygen-containing functional groups, but at temperature T 0.05 However, it does not fall under the category of aromatic compounds below 200°C. This is because quinone-type functional groups are extremely stable and sublimate without thermal decomposition during the carbonization process, resulting in virtually zero carbonization yield.
[0101] Note that the temperature T of the aromatic compound used as a carbon source 0.05This can be evaluated by thermogravimetric analysis. Specifically, using a differential thermal and thermogravimetric simultaneous measurement device, the temperature is raised from room temperature (25°C) to 500°C at a heating rate of 10°C / min under argon gas flow conditions, and the temperature T at which a 5% mass loss is reached is measured. 0.05 It can be obtained by calculating [the value].
[0102] Here, aromatic compounds include monocyclic aromatic compounds and aromatic compounds with two or more rings (polycyclic aromatic compounds with two or more rings, and non-polycyclic aromatic compounds with two or more rings). Note that aromatic compounds also include heterocyclic aromatic compounds. Monocyclic aromatic compounds include compounds having a benzene skeleton, and heteromembered rings (compounds having a pyridine skeleton, a pyrimidine skeleton, a triazine skeleton, a pyrrole skeleton, a furan skeleton, a triazine skeleton, etc.). Polycyclic aromatic compounds with two or more rings are compounds in which two or more aromatic rings are fused together, and include compounds having a naphthalene skeleton, an anthracene skeleton, an anthraquinone skeleton, a phenanthrenequinone skeleton, a nitrogen-containing tricyclic skeleton (e.g., 1-azaphenanthrene, 4-azaphenanthrene, 9-azaphenanthrene, 1,10-phenanthroline, 9-azaanthracene, 9,10-diazaanthracene, etc.), a pyrene skeleton, a perylene skeleton, a phenanthrene skeleton, a pentacene skeleton, a coronene skeleton, and the like. Non-condensed polycyclic aromatic compounds with two or more rings are compounds in which two or more aromatic rings are linked to each other directly or by bridging members (aliphatic hydrocarbon groups, nitrogen atoms, sulfur atoms, etc.), and examples include compounds having a biphenyl skeleton, compounds having a terphenyl skeleton, and compounds having a triphenylmethane skeleton.
[0103] As for the aromatic compound, from the viewpoint of improving carbon yield, it is preferably at least one selected from monocyclic aromatic compounds and bicyclic aromatic compounds (preferably bicyclic condensed polycyclic aromatic compounds), wherein the oxygen-containing functional group is a carboxyl group and the nitrogen-containing functional group is an amino group. As for the bicyclic aromatic compound, a bicyclic condensed polycyclic aromatic compound is preferred, and naphthalene is preferred.
[0104] As for aromatic compounds, from the viewpoint of improving carbon yield, compounds that are aromatic compounds with three or more rings, in which the oxygen-containing functional group is a carboxyl group or a hydroxyl group, and the nitrogen-containing functional group is an amino group are also preferred. As the aromatic compound with three or more rings, a condensed polycyclic aromatic compound with three or more rings is preferred, and it is preferable that it be at least one selected from compounds having an anthraquinone skeleton and compounds having an anthracene skeleton.
[0105] Here, from the viewpoint of improving carbon yield, the total number of oxygen atoms in all oxygen-containing functional groups in the aromatic compound is preferably 4 or more, and more preferably 4 to 8. Also, the total number of nitrogen atoms in all nitrogen-containing groups is preferably 2 or more, and more preferably 2 to 4. Furthermore, two or more carboxyl groups may form an anhydride. Two or more carboxyl groups may also form an alkyl metal salt. In other words, for example, an aromatic compound having one carboxylic acid anhydride group corresponds to an aromatic compound having two carboxyl groups. Furthermore, amino groups include primary amino groups, secondary amino groups, and tertiary amino groups. Examples of secondary amino groups include -NR. 1 H(R 1 Examples include alkyl groups having 1 to 6 carbon atoms. Examples of tertiary amino groups include -NR 2 R 3 (R 2 , R 3 Examples include alkyl groups having 1 to 6 carbon atoms, each independently. Among these, primary amino groups are preferred as amino groups.
[0106] From the viewpoint of improving carbon yield, the number of carbon atoms in the aromatic compound is preferably 6 to 30, more preferably 6 to 24, and even more preferably 10 to 20. Here, the number of carbon atoms in the aromatic compound includes the carbon atoms of oxygen-containing functional groups and nitrogen-containing functional groups.
[0107] Aromatic compounds having two or more carboxyl groups and being monocyclic or bicyclic include benzenedicarboxylic acid, naphthalenedicarboxylic acid, benzenetetracarboxylic anhydride, and naphthalenetetracarboxylic anhydride. Other examples include dicarboxylic acids of the nitrogen-containing heteromembered ring of benzene, dicarboxylic acids of the nitrogen-containing heteromembered ring of naphthalene, and their anhydrides.
[0108] Examples of aromatic compounds having two or more carboxyl groups and three or more rings include phenanthrene, anthracene, pyrene, and coronene polycarboxylic acids. Nitrogen-containing heteromembered rings of these aromatic compounds with three or more rings are also examples.
[0109] Examples of aromatic compounds having two or more hydroxyl groups and three or more rings include anthraquinone, phenanthrenequinone, dihydroxyanthraquinone, tetrahydroxyanthraquinone, and dihydroxyanthracene.
[0110] Aromatic compounds having two or more amino groups and being monocyclic or bicyclic include diaminobenzene, diaminonaphthalene, diamines having a nitrogen-containing benzene ring, and diamines having a nitrogen-containing naphthalene ring.
[0111] Examples of aromatic compounds having two or more amino groups and two or more rings include diaminoanthraquinone, diaminoanthracene, diaminophenanthrene, and triaminoanthraquinone.
[0112] <1-2. Mold Source> The mold source is not particularly limited; it can be any material that yields a mold carbon material by performing the second step of heat treatment together with the carbon source. Examples of mold sources include at least one selected from oxides, carbonates, sulfates, and hydroxides of magnesium and alkaline earth metals. Examples of alkaline earth metals include calcium, barium, and strontium.
[0113] Examples of the above materials include magnesium oxide, calcium oxide, barium oxide, strontium oxide, magnesium carbonate, calcium carbonate, barium carbonate, strontium carbonate, magnesium sulfate, calcium sulfate, barium sulfate, strontium sulfate, magnesium hydroxide, calcium hydroxide, barium hydroxide, strontium hydroxide, and the like.
[0114] Among these, the mold source is preferably at least one selected from magnesium and alkaline earth metals, carbonates, sulfates, and hydroxides; more preferably at least one selected from magnesium and calcium, carbonates, sulfates, and hydroxides; even more preferably at least one selected from magnesium carbonates, sulfates, and hydroxides; and most preferably magnesium carbonate. These mold sources make it easy to produce a mold carbon material that does not contain coarse particles, has a small average particle size, a uniform particle size distribution, low bulk density, and a large specific surface area. In other words, it makes it easy to produce a mold carbon material that satisfies requirements (A) to (D) (preferably requirements (A) to (E)).
[0115] <1-3. Mixing ratio of carbon source and mold source> The mixing ratio of the carbon source to the mold source in the mixture (carbon source / mold source, mol / mol) is preferably 0.2 or higher in molar ratio, and more preferably 0.2 to 15.0. By controlling the mixing ratio of the carbon source to the mold source, it becomes easier to obtain the desired mold carbon material of this disclosure (which does not contain coarse particles, has a small average particle size, a uniform particle size distribution, a low bulk density, and a large specific surface area). In other words, it becomes easier to obtain a mold carbon material that satisfies requirements (A) to (D) (preferably requirements (A) to (E)).
[0116] <2.Second process> In this process, the mixture obtained in the first step is heat-treated under an inert gas atmosphere to obtain mold carbon.
[0117] For the heat treatment, the mixture is heated under conditions such as an inert gas atmosphere (e.g., a noble gas atmosphere), with a heating rate of 5°C / min to 30°C / min, raising the temperature to 600-1200°C, and holding it at that temperature for 10 minutes to 200 minutes. Through heat treatment, the carbon source is carbonized, and simultaneously, the mold source is thermally decomposed and oxidized to obtain a composite of carbon and mold (for example, an oxide containing at least one of magnesium and an alkaline earth metal). The lower limit of the heating temperature should be set to a temperature above the minimum temperature required for the mold source to decompose into oxides, and 600°C is preferred. The upper limit of the heating temperature should be below the temperature at which metal carbides are formed, and 1200°C is preferred. Therefore, the heating temperature is preferably 600°C to 1200°C, and more preferably 800°C to 1100°C.
[0118] <3. Third step> In this process, the mold-containing carbon obtained in the second process, i.e., the composite of carbon and mold, is pulverized to obtain pulverized mold-containing carbon.
[0119] As for the grinding method, known grinding methods and conditions can be used. For example, wet bead mills, dry bead mills, jet mills, etc., can be used. The grinding conditions are not restricted, but the particle size distribution of the ground mold carbon, obtained by volume-based particle size measurement using laser light scattering, is defined as the common logarithm of the particle size when the cumulative amount passing through is 10%, 50%, and 90%, respectively, with the total cumulative amount set to 100%. 10 (μm), average particle size DA 50 (μm) 、 90% particle size DA 90 When (μm), the average particle size DA 50 It is less than 5.0 μm, (DA 90 -DA 10 ) / DA 50 It is preferable to use conditions for crushing the mold carbon until the ratio becomes less than 1.1.
[0120] Average particle size DA of crushed mold carbon 50 It is less than 5.0 μm, (DA 90 -DA 10 ) / DA 50 Grinding to a ratio of less than 1.1 can be performed, for example, by wet bead milling. Specifically, this can be achieved by using a planetary ball mill (for example, the Fritsch P-5 Classic Line planetary ball mill), placing zirconia beads with a diameter of 1-2 mm, water, and mold carbon in a zirconia container, and rotating it at a rotation speed of 180-400 rpm for 20-200 minutes. Note that the rotation speed mentioned above refers to the rotation speed of revolution. The rotation-to-orbit ratio varies depending on the planetary ball mill; in the case of the Fritsch P-5 Classic Line planetary ball mill exemplified above, the rotation-to-orbit ratio is 1:-2.19.
[0121] In the third step, the mold carbon may be pulverized and then subjected to heat treatment, or the pulverization and heat treatment of the mold carbon may be repeated multiple times. The heat treatment conditions are, for example, the heat treatment conditions for the second step. Furthermore, there are no particular restrictions on the conditions for multiple grinding steps; for example, the average particle size DA of the ground mold carbon is determined in the final grinding step. 50 It is less than 5.0 μm, (DA 90 -DA 10 ) / DA 50The grinding conditions should be such that the result is less than 1.1.
[0122] 10% particle size DA of crushed mold carbon 10 (μm), average particle size DA 50 (μm) 、 and 90% particle size DA 90 (μm) is the 10% particle size D of the template carbon material of this disclosure. 10 (μm), average particle size D 50 (μm) 、 and 90% particle size D 90 This value was measured using the same measurement method as (μm).
[0123] <4.Fourth step> In this process, the pulverized mold-containing carbon obtained in the third process, that is, the mold of the pulverized carbon-mold composite, is removed to obtain mold carbon material. Specifically, in this process, for example, the composite of pulverized carbon and mold (e.g., an oxide containing at least one of magnesium and an alkaline earth metal) is pickled to dissolve the mold in the pickling solution. This removes the mold from the carbon-mold composite, obtaining a mold carbon material. The acid used for pickling can be any acid that dissolves the mold, and sulfuric acid is a preferred example. After pickling, the mold carbon material is washed with water and dried.
[0124] <5. Fifth step> In this process, after the fourth step, the mold carbon material is heat-treated in an inert gas atmosphere at a heating temperature of 1000°C to 2600°C. For example, the mold carbon material is heated under conditions such as an inert gas atmosphere (e.g., a noble gas atmosphere), with a heating rate of 5°C / min to 30°C / min, raising the temperature to 1000°C to 2600°C, and holding it at that temperature for 10 minutes to 200 minutes. Heat treatment increases the crystallinity of the mold carbon material, improving its durability.
[0125] Through the above process, the template carbon material of this disclosure is obtained.
[0126] <Catalyst layer for polymer electrolyte fuel cell and polymer electrolyte fuel cell> This disclosure describes a polymer electrolyte fuel cell along with the catalyst layer for polymer electrolyte fuel cells. The catalyst layer for a polymer electrolyte fuel cell according to this disclosure includes a catalyst support made of a template carbon material. The polymer electrolyte fuel cell according to this disclosure has the catalyst layer for a polymer electrolyte fuel cell according to this disclosure. Specifically, the template carbon material of this disclosure can be applied, for example, to catalyst layers 150 and 160 provided in the polymer electrolyte fuel cell 100 shown in Figure 1. Figure 1 is a schematic diagram showing an example of the general configuration of the fuel cell of this disclosure. The polymer electrolyte fuel cell 100 shown in Figure 1 comprises separators 110 and 120, gas diffusion layers 130 and 140, catalyst layers 150 and 160, and an electrolyte membrane 170.
[0127] Separator 110 is the anode-side separator and introduces a reducing gas such as hydrogen into the gas diffusion layer 130. Separator 120 is the cathode-side separator and introduces an oxidizing gas such as oxygen or air into the gas diffusion condensation phase. The types of separators 110 and 120 are not particularly limited and any separator used in conventional fuel cells (e.g., polymer electrolyte fuel cells) may be used.
[0128] The gas diffusion layer 130 is the anode-side gas diffusion layer, which diffuses the reducing gas supplied from the separator 110 before supplying it to the catalyst layer 150. The gas diffusion layer 140 is the cathode-side gas diffusion layer, which diffuses the oxidizing gas supplied from the separator 120 before supplying it to the catalyst layer 160. The types of gas diffusion layers 130 and 140 are not particularly limited and can be any gas diffusion layer used in conventional fuel cells (e.g., polymer electrolyte fuel cells). Examples of gas diffusion layers 130 and 140 include porous carbon materials (carbon cloth, carbon paper, etc.) and porous metal materials (metal mesh, metal wool, etc.). A preferred example of gas diffusion layers 130 and 140 is a two-layer gas diffusion layer. Specifically, the gas diffusion layers 130 and 140 have a two-layer structure in which the layer on the separator 110 and 120 side is a gas diffusion fiber layer mainly composed of fibrous carbon material, and the layer on the catalyst layer 150 and 160 side is a micropore layer mainly composed of carbon black.
[0129] The catalyst layer 150 is the so-called anode. Within the catalyst layer 150, an oxidation reaction of the reducing gas occurs, generating protons and electrons. For example, when the reducing gas is hydrogen gas, the following oxidation reaction occurs. H2→2H + +2e - (E0=0V)
[0130] Protons generated by the oxidation reaction reach the catalyst layer 160 through the catalyst layer 150 and the electrolyte membrane 170. Electrons generated by the oxidation reaction reach the external circuit through the catalyst layer 150, the gas diffusion layer 130, and the separator 110. After performing work (generating electricity) in the external circuit, the electrons are introduced into the separator 120. Subsequently, the electrons reach the catalyst layer 160 through the separator 120 and the gas diffusion layer 140.
[0131] The configuration of the catalyst layer 150, which serves as the anode, is not particularly limited. The configuration of the catalyst layer 150 may be the same as that of a conventional anode, the same as that of the catalyst layer 160, or it may be a configuration that is even more hydrophilic than that of the catalyst layer 160.
[0132] The catalyst layer 160 is the so-called cathode. Within the catalyst layer 160, a reduction reaction of the oxidizing gas occurs, producing water. For example, when the oxidizing gas is oxygen gas or air, the following reduction reaction occurs. The water generated by the oxidation reaction, along with the unreacted oxidizing gas, is discharged to the outside of the polymer electrolyte fuel cell 100. O2 + 4H + +4e - →2H2O (E0=1.23V)
[0133] Thus, the polymer electrolyte fuel cell 100 generates electricity by utilizing the energy difference (potential difference) between the oxidation reaction and the reduction reaction. In other words, the electrons produced in the oxidation reaction perform work in the external circuit.
[0134] The catalyst layer 160 contains the carbon material for catalyst support of this disclosure. Specifically, the catalyst layer 160 includes the template carbon material for catalyst support of this disclosure, an electrolyte material (ionomer), and a catalyst component (platinum, etc.). This enhances the power generation performance within the catalyst layer 160, thereby improving the power generation performance of the polymer electrolyte fuel cell 100.
[0135] The catalyst loading rate in the catalyst layer 160 is not particularly limited, but is preferably 30% by mass or more and less than 80% by mass. Power generation performance is further enhanced when the catalyst loading rate is within this range. Here, the catalyst loading rate is expressed as the mass percentage of the catalyst component relative to the total mass of catalyst-supported particles (particles on which the catalyst component is supported on a template carbon material for the catalyst support). If the catalyst loading rate is less than 30% by mass, it may be necessary to thicken the catalyst layer 160 in order to make the polymer electrolyte fuel cell 100 suitable for practical use. On the other hand, if the catalyst loading rate is 80% by mass or more, catalyst aggregation is more likely to occur. Also, if the catalyst layer 160 becomes too thin, there is a possibility of flooding occurring.
[0136] The mass ratio I / C of the electrolyte material mass I to the catalyst support template carbon material mass C in the catalyst layer 160 is not particularly limited, but is preferably greater than 0.5 and less than 5.0. In this case, the pore network and the electrolyte material network can coexist, resulting in high power generation performance. On the other hand, if the mass ratio I / C is 0.5 or less, the electrolyte material network becomes poor, and the proton conduction resistance tends to increase. If the mass ratio I / C is 5.0 or more, the pore network may be fragmented by the electrolyte material. In either case, power generation performance may decrease.
[0137] Furthermore, the thickness of the catalyst layer 160 is not particularly limited, but it is preferably greater than 5 μm and less than 20 μm. In this case, oxidizing gases diffuse easily into the catalyst layer 160, and flooding is less likely to occur. If the thickness of the catalyst layer 160 is 5 μm or less, flooding is more likely to occur. If the thickness of the catalyst layer 160 is 20 μm or more, oxidizing gases diffuse less easily into the catalyst layer 160, and the catalytic components near the electrolyte membrane 170 become less effective. In other words, the catalyst utilization rate may decrease.
[0138] The electrolyte membrane 170 is composed of an electrolyte material having proton conductivity. The electrolyte membrane 170 introduces the protons generated in the oxidation reaction into the catalyst layer 160 (cathode). Here, the type of electrolyte material is not particularly limited, and any electrolyte material used in conventional fuel cells, such as polymer electrolyte fuel cells, may be used. Examples of suitable electrolyte materials include electrolyte resins. Examples of electrolyte resins include polymers into which phosphate groups, sulfonic acid groups, etc. Specifically, examples include perfluorosulfonic acid polymers and polymers into which benzenesulfonic acid, etc., have been introduced. Of course, the electrolyte material may be of other types. Examples of such electrolyte materials include inorganic electrolyte materials and inorganic-organic hybrid electrolyte materials. The polymer electrolyte fuel cell 100 may be a fuel cell that operates within the range of room temperature (25°C) to 150°C.
[0139] [Method for manufacturing solid polymer fuel cells] The method for manufacturing the polymer electrolyte fuel cell 100 is not particularly limited, and any conventional manufacturing method is acceptable. However, the catalyst support template carbon material of this disclosure is used for the catalyst support. Of the catalyst layers 150 and 160, it is preferable to use the catalyst support template carbon material of this disclosure for at least the catalyst support in the catalyst layer 160 which becomes the cathode. Of course, the catalyst support template carbon material of this disclosure may also be used for the catalyst support in both the catalyst layer 150 which becomes the anode and the catalyst layer 160 which becomes the cathode. [Examples]
[0140] Examples of the template carbon material of this disclosure will be described. <Example 1> First, as a carbon source, 20g of polyvinyl alcohol (Denka Poval B05-S, manufactured by Denka Co., Ltd.) (approximately 3 x 10) -4 (mol) 0.05 mol magnesium citrate was used as the mold source, and the two were mixed in a mortar for more than 10 minutes to obtain the mixture (first step). Next, the mixture was heated in a tubular furnace under Ar flow at a heating rate of 20°C / min to 500°C, and then heat-treated at 500°C for 3 hours to obtain mold-containing carbon (second step). Next, the mold-containing carbon obtained in the second step, water, and 2 mm diameter zirconia beads were added to a zirconia pot and ground using a planetary ball mill (Fritsch P-5 Classic Line planetary ball mill). The grinding conditions were a rotational speed of 250 rpm and a grinding time of 25 minutes. This yielded ground mold-containing carbon (third step). Next, the pulverized mold carbon and 20% by mass sulfuric acid were added to a round-bottom flask and heated at 105°C for 3 days to remove the mold. After that, the material was washed and the powder recovered by suction filtration, and the mold carbon material was obtained by vacuum drying at 90°C for more than 24 hours (fourth step). Since polyvinyl alcohol (PVA) is a polymer, its molecular weight has a distribution, and the molecular weight is only an average value. Therefore, the number of moles of polyvinyl alcohol and the molar ratio of the carbon source to the template source are for reference only.
[0141] <Example 2> In the first step, 0.05 mol of magnesium citrate (cit-Mg) was used as the carbon source, and 0.24 mol of barium carbonate was used as the mold source. In the second step, the heat treatment temperature was 1200°C and the heat treatment time was 2 hours. Otherwise, the first and second steps were carried out in the same procedure as in Example 1. The third step was carried out using the same procedure as in Example 1. In the fourth step, the procedure was carried out in the same manner as in Example 1, except that crushed mold carbon and hydrochloric acid with a concentration of 10% by mass were added to a round-bottom flask. A mold carbon material was obtained by following the procedure described above.
[0142] <Examples 3-7> The types and quantities of carbon source and mold source in the first step, heating temperature and heating time in the second step, and grinding conditions (revolution speed, grinding time, bead diameter) in the third step were as shown in Table 1. Otherwise, the mold carbon material was obtained using the same procedure as in Example 1.
[0143] <Example 8> The types and quantities of the carbon source and mold source in the first step, and the heating temperature and heating time in the second step were set to the conditions shown in Table 1, and the first and second steps were carried out in the same procedure as in Example 1. Next, as the third step, the obtained mold-containing carbon was pulverized under the conditions described in Table 1. The first pulverization was performed at a rotation speed of 250 rpm, a pulverization time of 25 minutes, and a bead diameter of 2 mm. The obtained pulverized mold-containing carbon was then heat-treated under the conditions described in Table 1 (1000°C, 1 hour). The pulverized and heat-treated mold-containing carbon was further pulverized under the conditions described in Table 1. The second pulverization was performed at a rotation speed of 180 rpm, a pulverization time of 20 minutes, and a bead diameter of 2 mm. Then, the fourth step was carried out in the same procedure as in Example 1 to obtain the final mold carbon material.
[0144] <Comparative Example 1> The types and quantities of carbon source and mold source in the first step, and the heating temperature and heating time in the second step were as shown in Table 1. Grinding was not performed in the third step. Otherwise, the mold carbon material was obtained using the same procedure as in Example 1.
[0145] <Comparative Examples 2-5> The first and second steps were carried out in the same procedure as in Example 1, with the types and amounts of carbon source and mold source in the first step, and the heating temperature and heating time in the second step being as shown in Table 1. Next, without performing the third step (crushing), the mold-containing carbon obtained in the second step was acid-washed using the same procedure as in the fourth step of Example 1 to remove the mold. Subsequently, the mold carbon material, from which the mold had been removed, was pulverized under the pulverization conditions (revolution speed, pulverization time) shown in Table 1. The pulverized mold carbon was dried to remove water, thereby obtaining the final mold carbon material.
[0146] <Comparative Example 6> As a commercially available carbon material for the mold, we prepared "Knobel MJ4030" manufactured by Toyo Tanso Co., Ltd. "Knobel MJ4030," water, and 2mm diameter zirconia beads were added to a zirconia pot and ground using a planetary ball mill (Fritsch P-5 Classic Line planetary ball mill) under the conditions shown in the table. The ground mold carbon was dried to remove the water and obtain the final mold carbon material.
[0147] <Comparative Example 7> The first and second steps were carried out in the same procedure as in Example 1, with the types and amounts of carbon source and mold source in the first step, and the heating temperature and heating time in the second step being as shown in Table 1. Next, without performing the third step (crushing), the mold-containing carbon obtained in the second step was acid-washed using the same procedure as in the fourth step of Example 1 to remove the mold. The mold carbon material, from which the mold had been removed, was pulverized twice under the pulverization conditions (revolution speed, pulverization time) shown in the table. The pulverized mold carbon was dried to remove water, thereby obtaining the final mold carbon material.
[0148] <Comparative Example 8> Magnesium oxide was pulverized under the conditions described in Table 1 (revolution speed 360 rpm, pulverization time 25 minutes, zirconia bead diameter 2 mm). Subsequently, in the first step, 20 g (approximately 3 x 10) of polyvinyl alcohol (Denka Poval B05-S, manufactured by Denka Co., Ltd.) was added as a carbon source. -4 As a mold source, 0.07 mol of pre-ground magnesium oxide was used. Otherwise, the first and second steps were carried out in the same procedure as in Example 1. Grinding was not performed in the third step. The fourth step was carried out in the same procedure as in Example 1 to obtain the mold carbon material.
[0149] <1. Evaluation> The following evaluations were performed on the mold carbon materials obtained for each example.
[0150] <1-1. Measurement of particle size distribution using laser light scattering method> Approximately 50 mg of sample was measured from the template carbon material sample in each example. Next, the sample was placed into the sample input tank of a laser diffraction particle size distribution analyzer (LA-960, Horiba, Ltd.) and the particle size distribution was measured. A 0.2% by mass aqueous solution of sodium hexametaphosphate was used as the solvent. Then, using a laser diffraction particle size distribution analyzer (LA-960, Horiba, Ltd.), the particle size distribution of the cumulative amount of particles passing through, from small to large, was obtained based on volume-based particle size. From this particle size distribution of the cumulative amount of particles passing through, the following particle sizes were determined. • Common logarithm of particle size when the cumulative amount passing through is 10%: 10% particle size D 10 (μm) • Common logarithm of particle size when the cumulative amount passing through is 50%: Average particle size D 50 (μm) • Common logarithm of particle size when the cumulative amount passing through is 90%: 90% particle size D 90 (μm)
[0151] Based on these particle sizes, the average particle size D of the mold carbon material is determined. 50、 (D 90 -D 10 ) / D 50 They sought it. Similarly, the average particle size DA of the pulverized mold carbon obtained in the third step of pulverization is 50 , (DA 90 -DA 10 ) / DA 50 They also requested it.
[0152] <1-2. Measurement of bulk density> The bulk density of the mold carbon material in each example was measured in accordance with JIS R 1628:1997. Specifically, the "bulk density" value of the mold carbon material in each example is the "tap bulk density" value from the bulk density described in JIS R 1628:1997.
[0153] <1-3. Measurement of nitrogen adsorption / desorption isotherms> The nitrogen adsorption / desorption isotherms of the template carbon materials for each example were measured using a method compliant with JIS K 6217-2:2017. Specifically, the following was done: Approximately 20 mg of sample was taken from the template carbon material of each example and vacuum-dried at 300°C for 2 hours. Next, the sample was placed in an automated specific surface area analyzer (BELSORP-MAX, manufactured by Microtrac-Bel), and nitrogen gas was used as the adsorbate. The nitrogen adsorption / desorption isotherm was measured at a measurement temperature of 77K. High-purity nitrogen gas (G1 grade, manufactured by Taiyo Nippon Sanso Corporation) was used for the measurement. The relative pressure was 1 × 10⁻⁶. ―6 For relative pressures up to ~0.1, approximately 40 measurements were taken, and for relative pressures above that, the settings were configured to take approximately one measurement for every 0.02 in relative pressure. Next, the BET specific surface area was calculated by performing a BET analysis on nitrogen adsorption isotherms in the relative pressure P / P0 range of 0.05 to 0.15. The analysis software included with the instrument was used for the BET analysis. Furthermore, the mesopore volume fraction was calculated from nitrogen adsorption isotherms using the analysis software included with the instrument. Specifically, the pore volume fraction V for pores with a diameter of 2 to 10 nm was calculated by dividing the pore volume of pores with a diameter of 2 to 10 nm by the total pore volume. 2-10 The following was calculated. Similarly, by dividing the pore volume of pores with a diameter of 2 to 50 nm by the total pore volume, the pore volume fraction V of pores with a diameter of 2 to 50 nm in the total pore volume was obtained. 2-50These were calculated separately.
[0154] <1-4. Evaluation of fuel cell performance> To confirm the high fluid diffusivity of each example's template carbon material, performance evaluations were conducted when each example's template carbon material was applied as a catalyst support for a polymer electrolyte fuel cell. Fluid diffusivity was judged by the high-load performance value when the template carbon material was used as a catalyst support for a polymer electrolyte fuel cell. The reason why high fluid diffusivity can be judged by the high-load performance value is as follows. High load performance is thought to be influenced not only by the utilization efficiency of the metal catalyst supported on the catalyst support (i.e., the fluid diffusivity within the particles of the template carbon material), but also by the diffusivity of the reaction gas when the catalyst is layered and the drainage of water produced by the reaction (i.e., the fluid diffusivity between the particles of the template carbon material). In this case, the gas diffusivity within the particles and the drainage of the generated water are important for the utilization efficiency of the catalyst. If the gas does not reach the catalyst, the power generation reaction will not occur, and if the generated water is not drained, it will cover the surface of the metal catalyst and prevent the reaction, or it will clog the pores of the catalyst support and prevent gas diffusion. Therefore, a template carbon material that exhibits high high load performance can be considered to have high gas and water diffusivity within and between the particles of the template carbon material.
[0155] Detailed measurement methods will be described later, but in this embodiment, the current value when the voltage between cell terminals drops to 0.3V was defined as high load performance, and high load performance of 1.2A or more was evaluated as "C" (excellent high load performance), 1.3A or more as "B" (even better high load performance), 1.35A or more as "A" (very good high load performance), and less than 1.2A as "D" (poor high load performance). The evaluation of high load performance for the mold carbon material in each example was performed as follows.
[0156] Finally, the template carbon material obtained for each example was heated in an Ar atmosphere at a heating rate of 20°C / min to 2000°C, and then heat-treated at 2000°C for 1 hour (corresponding to the fifth step) to obtain graphitized template carbon material. Using the obtained template carbon material, a catalyst for polymer electrolyte fuel cells carrying a catalytic metal was prepared in the following manner. Next, a catalyst layer ink liquid was prepared using the obtained catalyst. Then, the catalyst layer ink liquid was used to form a catalyst layer. Next, a membrane electrode assembly (MEA: Membrane Electrode Assembly) was fabricated using the formed catalyst layer. Then, the fabricated MEA was incorporated into a fuel cell unit, and a power generation test was performed using a fuel cell measurement device. Hereinafter, the preparation of each member and the cell evaluation by the power generation test will be described in detail.
[0157] <1-4-1. Preparation of Catalyst (Platinum)-Supported Template Carbon Material> The template carbon material of each example was dispersed in distilled water, formaldehyde was added to this dispersion, the mixture was placed in a water bath set at 40°C, and after the temperature of the dispersion reached 40°C, the same temperature as the bath, an aqueous nitric acid solution of dinitrodiammine Pt complex was slowly poured into the dispersion under stirring. Thereafter, stirring was continued for about 2 hours, followed by filtration, and the obtained solid was washed. The solid thus obtained was vacuum-dried at 90°C, pulverized in a mortar, and then subjected to heat treatment at 200°C for 1 hour in an argon atmosphere containing 5% by volume of hydrogen to produce a platinum-supported template carbon material. The platinum loading amount of this platinum-supported template carbon material was adjusted to be 40 mass% with respect to the total mass of the template carbon material and platinum particles, and was measured and confirmed by inductively coupled plasma atomic emission spectrometry (ICP-AES: Inductively Coupled Plasma - Atomic Emission Spectrometry).
[0158] <1-4-2. Preparation of Catalyst Layer> Using the platinum-supported templated carbon material (Pt catalyst) prepared as described above, and using Nafion (registered trademark: Nafion; a perfluorosulfonic acid-based ion exchange resin) manufactured by DuPont as the electrolyte resin, the Pt catalyst and Nafion were blended in an Ar atmosphere such that the mass of the Nafion solid content was 1.0 times the mass of the templated carbon material in the Pt catalyst. After gentle stirring, the Pt catalyst was crushed by ultrasonic waves, and ethanol was further added to adjust the total solid content concentration of the combined Pt catalyst and electrolyte resin to 1.0 mass%, thereby preparing a catalyst layer ink liquid in which the Pt catalyst and the electrolyte resin were mixed. Ethanol was further added to each catalyst layer ink liquid with a solid content concentration of 1.0 mass% prepared in this manner to produce a catalyst layer ink liquid for spray coating with a platinum concentration of 0.5 mass%. The spray conditions were adjusted so that the mass of platinum per unit area of the catalyst layer (hereinafter referred to as "platinum basis weight") was 0.2 mg / cm², and the catalyst layer ink for spray coating was sprayed onto a Teflon (registered trademark) sheet, followed by a drying treatment at 120°C for 60 minutes in argon to produce a catalyst layer.
[0159] <1-4-3. Fabrication of MEA> Using the catalyst layer produced as described above, an MEA (Membrane Electrode Assembly) was produced by the following method. A square electrolyte membrane with a side length of 6 cm was cut out from a Nafion membrane (NR211 manufactured by DuPont). In addition, each of the anode and cathode catalyst layers applied on the Teflon (registered trademark) sheet was cut into a square shape with a side length of 2.5 cm using a utility knife. The electrolyte membrane was sandwiched between the anode and cathode catalyst layers cut out in this manner, such that each catalyst layer was in contact with the center portion of the electrolyte membrane and there was no misalignment between them. The assembly was pressed at 120°C and 100 kg / cm² for 10 minutes, then cooled to room temperature, after which only the Teflon sheets were carefully peeled off from both the anode and cathode, to prepare a catalyst layer-electrolyte membrane assembly in which the anode and cathode catalyst layers were fixed to the electrolyte membrane.
[0160] Next, as a gas diffusion layer, a pair of square carbon papers measuring 2.5 cm on each side were cut from carbon paper (SGL Carbon 35BC). The catalyst layer-electrolyte membrane assembly was then placed between these carbon papers so that the anode and cathode catalyst layers were aligned and not misaligned, and the temperature was set at 120°C and 50 kg / cm². 2 The MEA was then pressed for 10 minutes to produce it. Furthermore, the basis weight of each component of the catalyst metal, template carbon material, and electrolyte material in each fabricated MEA was calculated by determining the mass of the catalyst layer fixed to the Nafion film (electrolyte film) from the difference between the mass of the Teflon sheet with the catalyst layer attached before pressing and the mass of the Teflon sheet peeled off after pressing, and then calculating the basis weight from the mass ratio of the catalyst layer composition.
[0161] <1-4-4. Fuel Cell Performance Evaluation> For each example, the MEA fabricated using the specified carbon template material was assembled into a cell, set in a fuel cell measurement device, and the fuel cell performance was evaluated according to the following procedure. For the reaction gas, air was supplied to the cathode and pure hydrogen to the anode, with the pressure adjusted by a back pressure valve located downstream of the cell under atmospheric pressure to achieve utilization rates of 40% and 70%, respectively, resulting in a back pressure of 0.04 MPa. The cell temperature was set to 80°C, and the reaction gas supplied to both the cathode and anode was bubbled with distilled water maintained at 60°C in a humidifier. Power generation was evaluated by supplying 60°C humidified gas to an 80°C cell.
[0162] Under these conditions, with the reaction gas supplied to the cell, the current was increased by 5 mA / cm² every second. The current value at which the voltage between the cell terminals dropped to 0.3 V was defined as the high-load performance, and a fuel cell power generation performance evaluation test was conducted.
[0163] [Table 1-1]
[0164] [Table 1-2]
[0165] From the results shown in Table 1 above, it can be seen that in Examples 1 to 8, mold carbon materials were obtained that did not contain coarse particles, had a small average particle size, a uniform particle size distribution, low bulk density, and a large specific surface area. Furthermore, since all of these showed good high-load performance, it can be said that the mold carbon materials of Examples 1 to 7 have high fluid diffusivity when closely packed.
[0166] In particular, average particle size D 50 The particle size is less than 3.5 μm, and the bulk density is 0.05 g / cm³. 3 Larger 0.1 g / cm³ 3 The pore volume fraction V for pores with a diameter of 2-10 nm in the total pore volume is less than the total pore volume. 2-10 The pore volume ratio V is between 25% and 45% of the total pore volume, with pore diameters of 2 to 50 nm. 2-50 The mold carbon materials of Examples 4-8, in which the carbon content was between 45% and 75%, exhibited particularly excellent high-load performance and especially high fluid diffusivity.
[0167] Example 8 shows a case where mold-in-the-mold grinding is repeated, and heat treatment is performed between the first and second grinding cycles. Since the grinding is performed with the mold in place, even when grinding is performed, the mold carbon material does not collapse due to damage from grinding, and the generation of aggregated particles (coarse particles) due to the generation of fine powder, as well as the collapse of the pore structure, can be suppressed. This effect can be maintained even when grinding is repeated multiple times. Furthermore, this effect can be maintained even when heat treatment is performed between multiple grinding cycles. Therefore, even if grinding is performed twice in the third step, and heat treatment is performed in between, a mold carbon material can be obtained that does not contain coarse particles, has a small average particle size, and a uniform particle size distribution. For this reason, the mold carbon material of Example 8 has excellent high load performance and exhibits high fluid diffusivity.
[0168] In contrast, Comparative Examples 1 to 8 failed to produce a mold carbon material that was free of coarse particles, had a small average particle size, a uniform particle size distribution, low bulk density, and a large specific surface area. As a result, the mold carbon materials of Comparative Examples 1 to 8 had poor high-load performance and low fluid diffusivity when closely packed.
[0169] Comparative Example 1 shows the case where grinding is not performed. When grinding is not performed, the average particle size D 50 The average particle size is large, exceeding 5.0 μm. Furthermore, the presence of coarse particles results in an uneven particle size distribution, exhibiting a wide distribution (D 90 -D 10 ) / D 50 The value exceeds 1.1, which is large. Therefore, a mold carbon material free of coarse particles, with a small average particle size and a uniform particle size distribution could not be obtained. As a result, the mold carbon material of Comparative Example 1 has poor high-load performance and therefore has poor fluid diffusivity when closely packed.
[0170] Comparative Examples 2-6 show the case where grinding was not performed with the mold included in the third step, but rather by performing normal grinding (grinding the mold carbon material after removing the mold). Even after adjusting the grinding conditions, it was not possible to obtain mold carbon material that did not contain coarse particles, had a small average particle size, a uniform particle size distribution, low bulk density, and a large specific surface area. When the grinding strength was weak, the average particle size D 50 It is not possible to reduce the size. When the crushing strength is high, the average particle size D 50 The size decreases, but fine particles are generated and agglomeration occurs, so the particle size distribution width is shown (D 90 -D 10 ) / D 50 If the grinding force is large, and if the pore structure of the mold carbon material collapses due to damage from grinding, a large specific surface area cannot be obtained. If the grinding force is even stronger, a large number of fine particles are generated and many aggregates occur, so the number of coarse particles increases, and the average particle size D 50 The size is large and shows the particle size distribution width (D 90 -D 10 ) / D 50 The size also increases. Furthermore, due to the wide particle size distribution, the bulk density is high, and a large specific surface area cannot be obtained due to damage from grinding. Note that the average particle size D50 While a larger particle size tends to result in lower bulk density, a wider particle size distribution can lead to higher bulk density. Consequently, it is not possible to obtain a mold carbon material that does not contain coarse particles, has a small average particle size, a uniform particle size distribution, low bulk density, and a large specific surface area. Therefore, the mold carbon materials of Comparative Examples 2-6 exhibit poor high-load performance, resulting in low fluid diffusivity when closely packed.
[0171] Comparative Example 7 shows the case where the third step of grinding, which includes the mold, is not performed, and normal grinding (grinding the mold carbon material after removing the mold) is performed twice. In the first grinding, a mold carbon material free of coarse particles, with a small average particle size and a uniform particle size distribution was not obtained. In the second grinding, the aim was to reduce the average particle size and make the particle size distribution uniform, but while the average particle size was reduced, the particle size distribution width was shown (D 90 -D 10 ) / D 50 The particle size distribution remained uneven. This is because even if coarse particles are reduced in size by grinding, new aggregated particles are created by the fine powder generated during grinding. Because the particle size distribution remained uneven, the bulk density increased, and furthermore, the pore structure collapsed due to damage from the two grinding processes, resulting in a decrease in specific surface area. Therefore, even when performing two normal grinding processes, and adjusting the grinding conditions as in Comparative Examples 2-6, it was not possible to obtain a mold carbon material that did not contain coarse particles, had a small average particle size, a uniform particle size distribution, low bulk density, and a large specific surface area, resulting in poor high-load performance. Consequently, the mold carbon material of Comparative Example 7 has poor fluid diffusivity when closely packed.
[0172] Comparative Example 8 shows the case where only the magnesium oxide particles (MgO particles), which are the template source, are crushed first. When only MgO particles are crushed first, the MgO crystallites are not coated with carbon during crushing, so when crushed, the MgO crystallites deform, aggregate, and fine powder is generated due to damage from the crushing. As a result, the average particle size D of the final template carbon material is affected by the presence of aggregated particles. 50The particle size distribution becomes larger. Furthermore, the presence of fine particles results in an uneven distribution of particles. Consequently, fluid diffusivity within and between particles decreases, leading to poor high-load performance. Therefore, the mold carbon material of Comparative Example 8 exhibits poor fluid diffusivity when closely packed. [Explanation of symbols]
[0173] 100 Polymer electrolyte fuel cell 110, 120 Separator 130, 140 Gas diffusion layer 150, 160 catalyst layer 170 Electrolyte membrane
Claims
1. A mold carbon material that satisfies the following requirements (A), (B), (C), and (D). (A) In the particle size distribution of the template carbon material obtained by volume-based particle size scale using the laser light scattering method, the common logarithm of the particle size when the total cumulative amount is 100% and the cumulative amount is 50% is the average particle size D. 50 When (μm), the average particle size D 50 It is less than 5.0 μm. (B) In the particle size distribution of a template carbon material of the cumulative undersize amount from small particles to large particles obtained as a volume-based particle size by a laser light scattering method, the total cumulative amount is taken as 100%, and the common logarithm values of the particle sizes when the cumulative undersize amount is 10%, 50%, and 90% respectively are respectively defined as 10% particle diameter D 10 (μm), average particle diameter D 50 (μm) 、 90% particle diameter D 90 (μm), (D 90 -D 10 ) / D 50 is less than 1.
1. (C) Bulk density of 0.01 g / cm³ 3 Larger 0.10 g / cm 3 It is less than. (D) BET specific surface area is 500 m 2 / g or more 2000m 2 It is less than or equal to / g.
2. The aforementioned bulk density is 0.05 g / cm³. 3 Larger 0.10 g / cm 3 A mold carbon material according to claim 1, which is less than [amount missing].
3. The mold carbon material according to claim 1, further satisfying the following requirement (E). (E) V, the pore volume fraction of pores with a diameter of 2-10 nm in the total pore volume. 2-10 The pore volume ratio V is 25% to 45% and the pore diameter of 2 to 50 nm in the total pore volume. 2-50 The percentage is between 45% and 75%.
4. The average particle size D 50 The template carbon material according to claim 1, wherein the particle size is less than 3.5 μm.
5. A catalyst layer for a polymer electrolyte fuel cell comprising a catalyst support made of a template carbon material according to any one of claims 1 to 4.
6. A polymer electrolyte fuel cell comprising a catalyst layer for a polymer electrolyte fuel cell as described in claim 5.
7. A method for manufacturing a mold carbon material comprising the following steps 1 to 4. (1) The first step of mixing the carbon source and the mold source to obtain the mixture. (2) A second step in which the mixture is heat-treated under an inert gas atmosphere to obtain mold carbon. (3) A third step in which the mold carbon is crushed to obtain crushed mold carbon. (4) Fourth step: Remove the mold from the pulverized mold carbon to obtain mold carbon material.
8. In the third step, the particle size distribution of the pulverized mold carbon, obtained by volume-based particle size measurement using the laser light scattering method, is calculated by setting the total cumulative amount to 100% and the common logarithms of the particle size when the cumulative amount is 10%, 50%, and 90%, respectively, as the 10% particle size DA. 10 (μm), average particle size DA 50 (μm) 、 90% particle size DA 90 When (μm), the average particle size DA 50 It is less than 5.0 μm, (DA 90 -DA 10 ) / DA 50 A method for producing a mold carbon material according to claim 7, comprising grinding the mold carbon containing the mold until the result is less than 1.
1.
9. The method for producing a mold carbon material according to claim 7, wherein the heating temperature in the second step is 600°C or more and 1200°C or less.
10. The method for producing a mold carbon material according to claim 7, wherein the heating temperature in the second step is 800°C or more and 1100°C or less.
11. The method for producing a mold carbon material according to claim 7, wherein in the first step, the mixing ratio of the carbon source to the mold source in the mixture is 0.2 or more in molar terms.
12. A method for producing a mold carbon material according to claim 7, further comprising the following fifth step. (5) A fifth step in which, after the fourth step, the mold carbon material is heat-treated in an inert gas atmosphere at a heating temperature of 1000°C to 2600°C.
13. The method for producing a mold carbon material according to claim 7, wherein the mold source in the first step is at least one selected from magnesium and alkaline earth metals, oxides, carbonates, sulfates, and hydroxides.
14. The method for producing a mold carbon material according to claim 7, wherein the mold source in the first step is at least one selected from magnesium and alkaline earth metals, carbonates, sulfates, and hydroxides.
15. The method for producing a mold carbon material according to claim 7, wherein the mold source in the first step is at least one selected from magnesium and calcium carbonates, sulfates, and hydroxides.
16. The method for producing a mold carbon material according to claim 7, wherein the mold source in the first step is at least one selected from magnesium carbonate, magnesium sulfate, and magnesium hydroxide.
17. The method for producing a mold carbon material according to claim 7, wherein the mold source in the first step is a magnesium carbonate.
18. The method for producing a mold carbon material according to claim 7, wherein the carbon source in the first step includes a carbon source that satisfies at least one of the following requirements (a), (b), and (c). (a) an aliphatic hydrocarbon compound having two or more carboxyl groups, and having a structure in which two to four carbon atoms are interposed between at least two of the carboxyl groups. (b) A mixture comprising a low molecular weight compound A having two or more functional groups A and a low molecular weight compound B having two or more functional groups B, wherein at least one of the low molecular weight compound A and the low molecular weight compound B is an aromatic compound, and which, upon heating, can be formed by chemical bonding between the functional groups A and B to create a polymer compound in which the low molecular weight compound A and the low molecular weight compound B are alternately bonded. (c) Having at least two oxygen-containing functional groups and at least two nitrogen-containing functional groups, and reaching a temperature T of 5% mass loss in thermogravimetric analysis under an inert atmosphere. 0.05 Aromatic compounds below 200°C.
Citation Information
Patent Citations
Porous carbon material and method of producing the same
JP2015164889A
Template carbon material for fuel cell catalyst carrier, method of producing template carbon material for fuel cell catalyst carrier, catalyst layer for fuel cell, and fuel cell
JP2019012601A
Carbon material for catalyst carrier, catalyst layer for fuel cell, and fuel cell
JP2020166941A
Porous carbon particle, porous carbon particle dispersion, and method for producing the same
JP2021178772A